Nonaqueous electrolyte secondary battery and method of manufacturing same
Patent Information
- Application Number
- JP2021574151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-01-29
AI Technical Summary
【0014】 本発明で特定する非水系電解液を用いることで、低温出力特性を向上させることができる非水系電解液二次電池を得ることが可能となり、併せて当該非水系電解液二次電池を製造することが可能となる。
Smart Images

Figure 0007617041000001 
Figure 0007617041000002 
Figure 0007617041000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a non-aqueous electrolyte solution and an energy device using the same. [Background technology]
[0002] Energy devices using nonaqueous electrolytes, such as nonaqueous electrolyte secondary batteries, electric double layer capacitors, and lithium ion capacitors, have been put to practical use in a wide range of applications, from so-called consumer power sources for mobile phones, notebook computers, etc., to on-board power sources for driving automobiles, etc., and large stationary power sources, etc. However, in recent years, there has been an increasing demand for higher performance in energy devices, and in particular, for nonaqueous electrolyte secondary batteries, there is a demand to achieve high levels of battery characteristics, such as capacity, input / output and charge / discharge rate characteristics, and safety.
[0003] In particular, when lithium secondary batteries are used as the power source for electric vehicles, the electric vehicles require a large amount of energy when starting and accelerating, and the large amount of energy generated when decelerating must be efficiently regenerated, so the lithium secondary batteries are required to have high output and input characteristics. In addition, because electric vehicles are used outdoors, in order for the electric vehicles to be able to start and accelerate quickly even in cold weather, the lithium secondary batteries are required to have high input and output characteristics (low internal battery impedance) especially at low temperatures such as -20°C.
[0004] To date, many techniques have been studied for improving the initial characteristics of non-aqueous electrolyte secondary batteries, including the active materials of the positive and negative electrodes and the non-aqueous electrolyte. A technique for adding lithium fluorosulfonate (FSO3Li) to the non-aqueous electrolyte to improve the low-temperature performance of non-aqueous electrolyte secondary batteries is known (for example, Patent Document 1).
[0005] Furthermore, Patent Document 2 discloses a technology for providing a nonaqueous electrolyte secondary battery or the like having excellent input / output characteristics by using a nonaqueous electrolyte solution containing lithium difluorophosphate (LiPO2F2) and lithium bis(oxalatoborate) (LiBOB) and further containing a salt having an FS bond in the molecule. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2019-50153 A [Patent Document 2] JP 2016-184462 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, in recent years, there has been an increasing demand for higher performance non-aqueous electrolyte secondary batteries, and there is a demand for further improvement in the performance of non-aqueous electrolyte secondary batteries, in particular, improvement in input / output characteristics at low temperatures. On the other hand, especially during the first charging stage after the battery assembly process, a film called solid electrolyte interphase (SEI) is formed on the negative electrode. This SEI is closely related to battery performance such as battery capacity, output characteristics, and durability, and it is generally known that a dense and uniform SEI is formed and battery performance is improved by reducing the initial charging current value, stopping charging midway and leaving the battery to stand, etc.
[0008] However, as a result of extensive research by the present inventors, it has been found that in nonaqueous electrolyte secondary batteries using the electrolytes described in Patent Documents 1 and 2, if the aging temperature is not sufficiently high in the initial charge / discharge, aging, and inspection process (hereinafter also referred to as "battery break-in") after the battery assembly process, the output characteristics become insufficient in a low-temperature environment.
[0009] The above-mentioned "charge / discharge, aging, and inspection processes (battery break-in)" includes some or more of the charge / discharge, aging, and shipping inspection processes that are commonly and generally carried out in the manufacturing process of lithium-ion batteries after the battery assembly process (see, for example, "Automotive Technology for Lithium Secondary Batteries, Deterioration, Troubles, and Countermeasures," Technical Information Association, First Edition published on August 5, 2011).
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a nonaqueous electrolyte secondary battery capable of improving low-temperature output characteristics. [Means for solving the problem]
[0011] The inventors have studied the cause of this phenomenon and speculated that it is as follows. That is, in a battery using a non-aqueous electrolyte containing lithium bis(oxalato)borate and lithium difluorophosphate, if the aging temperature in the aging step after the battery assembly step is too low, the reduction reaction of the electrolyte on the negative electrode surface becomes non-uniform, the amount of the film formed on the negative electrode surface varies, and some parts of the negative electrode surface have a large amount of film and some parts have a small amount of film. If the above-mentioned input / output test is performed under such circumstances, the resistance of the parts with a large amount of film is large, so that the battery output decreases. On the other hand, by setting the aging temperature sufficiently high, the reduction reaction of the electrolyte on the negative electrode surface occurs uniformly, and a uniform film is formed on the negative electrode surface, improving the battery output. Patent Documents 1 and 2 disclose a technique for providing a nonaqueous electrolyte secondary battery having excellent input / output characteristics by using a combination of lithium fluorosulfonate, lithium difluorophosphate, and lithium bis(oxalato)borate. However, these techniques cannot prevent the above-mentioned phenomenon of non-uniformity of the negative electrode film, and there is still room for further improvement in the characteristics.
[0012] Therefore, the present inventors conducted extensive research to solve the above problems, and as a result, discovered that the output characteristics of a nonaqueous electrolyte secondary battery in a low-temperature environment can be improved by using a nonaqueous electrolyte solution containing fluorosulfonate ions, difluorophosphate ions, and bisoxalatoborate ions, in which the contents of fluorosulfonate ions, difluorophosphate ions, and bisoxalatoborate ions in the nonaqueous electrolyte solution are within specific ranges, and thus arrived at the present invention.
[0013] That is, the present invention provides specific embodiments as shown in [1] to [7] below. [1] A non-aqueous electrolyte secondary battery comprising a non-aqueous electrolyte containing fluorosulfonate ions, difluorophosphate ions, and bis(oxalato)borate ions, The non-aqueous electrolyte has a concentration of fluorosulfonate ions [FSO3 - ] and the concentration of difluorophosphate ion [PO2F2 - ] and the concentration of bis(oxalate)borate ions [BOB - and n is a nonaqueous electrolyte that satisfies the following formula (1): [FSO3 - ]>[PO2F2 - ]>[BOB - ] (1) [2] The nonaqueous electrolyte secondary battery according to [1], wherein the nonaqueous electrolyte satisfies the following formulas (2) and (3): ([FSO3 - ]+[PO2F2 - ]) / ([PO2F2 - ]+[BOB - ])>1.8 (2) [FSO3 - ]<1.3 Mass% (3) [3] The nonaqueous electrolyte secondary battery according to [1] or [2], wherein the voltage change when the nonaqueous electrolyte secondary battery is stored for 24 hours at a voltage of 4.1 V in a high temperature environment of 60° C. or higher is 33 mV or more. [4] The nonaqueous electrolyte secondary battery according to any one of [1] to [3], wherein the nonaqueous electrolyte contains Al ions in an amount of 1 ppm by mass or more and 100 ppm by mass or less. [5] A non-aqueous electrolyte secondary battery comprising a negative electrode and a positive electrode capable of absorbing and releasing lithium ions, and the non-aqueous electrolyte according to any one of [1] to [4]. [6] The nonaqueous electrolyte secondary battery according to [5], wherein the positive electrode has a positive electrode active material layer on a current collector, and the positive electrode active material layer contains at least one selected from the group consisting of lithium-cobalt composite oxide, lithium-cobalt-nickel composite oxide, lithium-manganese composite oxide, lithium-cobalt-manganese composite oxide, lithium-nickel composite oxide, lithium-nickel composite oxide, lithium-nickel-manganese composite oxide, and lithium-cobalt-nickel-manganese composite oxide. [7] A method for producing a nonaqueous electrolyte secondary battery comprising a nonaqueous electrolyte solution containing fluorosulfonate ions, difluorophosphate ions, and bis(oxalato)borate ions, comprising the steps of: The concentration of fluorosulfonate ions in the non-aqueous electrolyte [FSO3 - ] and the concentration of difluorophosphate ion [PO2F2 - ] and the concentration of bis(oxalate)borate ions [BOB - a battery assembly process for assembling a nonaqueous electrolyte secondary battery using a nonaqueous electrolyte solution in which an aging step of aging the nonaqueous electrolyte secondary battery in a temperature environment ranging from 50°C to 80°C. [FSO3 - ]>[PO2F2 - ]>[BOB - ] (1) Effect of the Invention
[0014] By using the nonaqueous electrolyte specified in the present invention, it is possible to obtain a nonaqueous electrolyte secondary battery capable of improving low-temperature output characteristics, and also to manufacture the nonaqueous electrolyte secondary battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, the embodiments of the present invention will be described in detail. The following embodiments are examples (representative examples) of the present invention, and the present invention is not limited to these. Furthermore, the present invention can be modified and carried out as desired without departing from the gist of the present invention.
[0016] <1.Non-aqueous electrolyte> The non-aqueous electrolyte used in the non-aqueous secondary battery according to one embodiment of the present invention contains fluorosulfonate ions (FSO - ), difluorophosphate ion (PO2F2 - ) and bis(oxalate)borate ion (BOB - ), the contents of which are within specific ranges.
[0017] In addition, the non-aqueous electrolyte preferably contains Al ions in an amount of 1 ppm by mass to 100 ppm by mass. By containing specific amounts of Al ions, fluorosulfonate ions, difluorophosphate ions, and bis(oxalato)borate ions in the non-aqueous electrolyte, the Al ions are converted into FSO3 - (fluorosulfonate ion) or PO2F2 - It is presumed that the coordination or interaction of one or more of the following ions increases the reduction resistance of the Al ions, suppressing the negative electrode reduction reaction, thereby improving the charged storage characteristics in high-temperature environments. The non-aqueous electrolyte will be described in detail below.
[0018] <1-1. Ingredients contained in non-aqueous electrolyte> <1-1-1. Fluorosulfonate ion (FSO3 - )> The non-aqueous electrolyte of this embodiment is FSO3 -As the counter ion of the fluorosulfonate ion, a monovalent cation or a divalent cation can be used. As the monovalent cation, a lithium ion, a sodium ion, or a potassium ion is preferable, and a lithium ion is particularly preferable. As the divalent cation, a magnesium ion or a calcium ion is preferable, and a magnesium ion is particularly preferable. These can be used alone or in combination of two or more. In a particularly preferred embodiment, FSO3 - is contained in the non-aqueous electrolyte as lithium fluorosulfonate (FSO3Li). FSO3 - The content of FSO3 is <1-2. - , PO2F2 - and B.O.B. - There are no particular limitations as long as the relationship described below is satisfied. - The content of FSO3 in the non-aqueous electrolyte is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.10% by mass or more. On the other hand, although there is no particular upper limit, it is preferably 10.0% by mass or less, more preferably 7.0% by mass or less, even more preferably 5.0% by mass or less, particularly preferably 4.0% by mass or less, and particularly preferably 3.0% by mass or less. - The content of in the non-aqueous electrolyte is preferably 0.002% by mass or more, more preferably 0.02% by mass or more, and even more preferably 0.20% by mass or more. On the other hand, although there is no particular upper limit, it is preferably 20.0% by mass or less, more preferably 14.0% by mass or less, even more preferably 10.0% by mass or less, particularly preferably 8.0% by mass or less, and particularly preferably 6.0% by mass or less. When a monovalent cation and a divalent cation are used in combination as a counter ion of the fluorosulfonate ion, the above-mentioned FSO3 - In this specification, the concentration of FSO3 in a non-aqueous electrolyte solution is adjusted to the range. - The content (mass%) of fluorosulfonate ions in the non-aqueous electrolyte ([FSO3 - ]) are synonymous.
[0019] FSO3 - When the content of FSO3 is 10.0 mass% or less in the non-aqueous electrolyte, the negative electrode reduction reaction does not increase so much that the internal resistance of the non-aqueous electrolyte secondary battery increases, which is preferable. When the content of FSO3 is 0.001 mass% or more, - Therefore, within the above range, the negative electrode reduction reaction in a high-temperature environment is suppressed, and thus the charged storage characteristics in a high-temperature environment can be improved.
[0020] FSO3 - The FSO3 in the nonaqueous electrolyte and the nonaqueous electrolyte secondary battery may be synthesized by a known method and used, or may be a commercially available product. - The method for measuring the content is not particularly limited, and any known method can be used. Specifically, ion chromatography, 19 F nuclear magnetic resonance spectroscopy (hereinafter sometimes referred to as "NMR") and the like.
[0021] <1-1-2. Difluorophosphate ion (PO2F2 - )> The non-aqueous electrolyte of this embodiment is PO2F2 - As the counter ion of the difluorophosphate ion, a monovalent cation or a divalent cation can be used. As the monovalent cation, a lithium ion, a sodium ion, or a potassium ion is preferable, and a lithium ion is particularly preferable. As the divalent cation, a magnesium ion or a calcium ion is preferable, and a magnesium ion is particularly preferable. These can be used alone or in combination of two or more. In a particularly preferred embodiment, PO2F2 - is contained in the non-aqueous electrolyte as lithium difluorophosphate (LiPO2F2). PO2F2 - The content of FSO3 is <1-2. - , PO2F2 - and B.O.B. -There is no particular limitation as long as the relationship described below is satisfied. Specifically, when a monovalent cation is used, - The lower limit of the content is preferably 0.001% by mass or more, more preferably 0.010% by mass or more, and even more preferably 0.10% by mass or more, based on the total amount of the non-aqueous electrolyte. The upper limit is preferably 1.3% by mass or less, more preferably 1.2% by mass or less, and even more preferably 1.1% by mass or less, based on the total amount of the non-aqueous electrolyte. - The lower limit of the content is preferably 0.002 mass% or more, more preferably 0.020 mass% or more, and even more preferably 0.20 mass% or more, based on the total amount of the nonaqueous electrolyte. The upper limit is preferably 2.6 mass% or less, more preferably 2.4 mass% or less, and even more preferably 2.2 mass% or less, based on the total amount of the nonaqueous electrolyte. When a monovalent cation and a divalent cation are used in combination as a counter ion of the difluorophosphate ion, the above-mentioned PO2F2 - In this specification, the concentration of PO2F2 in a non-aqueous electrolyte solution is adjusted to the range. - The content (mass%) of difluorophosphate ions in the nonaqueous electrolyte ([PO2F2 - ]) are synonymous.
[0022] PO2F2 - When the concentration is within the above preferred range, the effect of improving the initial output in a low-temperature environment is more easily achieved.
[0023] Here, PO2F2 - The preparation of the electrolyte in the case where LiPO2F2 is contained in the electrolyte may be performed by a known method and is not particularly limited. For example, LiPO2F2 synthesized by a different known method is added to the electrolyte, or water is made to coexist in the battery components such as the active material and the electrode plate, and when the battery is assembled using the electrolyte containing LiPF6, PO2F2 is added in the system. -In the present embodiment, either method may be used.
[0024] The above non-aqueous electrolyte and PO2F2 in non-aqueous electrolyte secondary batteries - The method for measuring the content is not particularly limited, and any known method can be used. Specifically, ion chromatography, 19 F NMR and the like.
[0025] <1-1-3. Bis(oxalate)borate ion (BOB - )> The non-aqueous electrolyte of this embodiment contains bis(oxalate)borate ions (BOB - ) As the counter ion of the bis(oxalato)borate ion, a monovalent cation or a divalent cation can be used. As the monovalent cation, a lithium ion, a sodium ion, or a potassium ion is preferable, and a lithium ion is particularly preferable. As the divalent cation, a magnesium ion or a calcium ion is preferable, and a magnesium ion is particularly preferable. These can be used alone or in combination of two or more. In a particularly preferred embodiment, the bis(oxalato)borate ion is contained in the nonaqueous electrolyte as lithium bis(oxalato)borate (LiBOB). BOB - The content of FSO3 is <1-2. - , PO2F2 - and B.O.B. - There is no particular limitation as long as the relationship described later in the section "Relationship between the cations" is satisfied. Specifically, when a monovalent cation is used, - The lower limit of the content is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.10% by mass or more, based on the total amount of the non-aqueous electrolyte. The upper limit is preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.8% by mass or less, based on the total amount of the non-aqueous electrolyte. -The lower limit of the content is preferably 0.002 mass% or more, more preferably 0.02 mass% or more, and even more preferably 0.20 mass% or more, based on the total amount of the non-aqueous electrolyte. The upper limit is preferably 4 mass% or less, more preferably 2 mass% or less, and even more preferably 1.6 mass% or less, based on the total amount of the non-aqueous electrolyte. When a monovalent cation and a divalent cation are used in combination as a counter ion of the bisoxalate borate ion, the above-mentioned BOB - In this specification, the BOB in a non-aqueous electrolyte solution is - The content (mass%) of bis(oxalatoborate) ions in the non-aqueous electrolyte ([BOB - ]) are synonymous.
[0026] BOB - When the concentration is within the above preferred range, the effect of improving the battery durability, such as high-temperature storage characteristics and cycle characteristics, is more easily achieved.
[0027] BOB - may be synthesized by a known method and used, or may be a commercially available product. - The preparation of the electrolyte solution when the electrolyte solution contains LiBOB may be carried out by a known method, and is not particularly limited. For example, a method of adding LiBOB synthesized by a different known method to the electrolyte solution can be mentioned. In the present embodiment, either method may be used. The above-mentioned non-aqueous electrolyte solution and the BOB in the non-aqueous electrolyte secondary battery - The method for measuring the content is not particularly limited, and any known method can be used. Specifically, ion chromatography, 11 B NMR, etc. - The method of analysis by ion chromatography is explained. The non-aqueous electrolyte solution is collected in a measuring flask, and the volume is adjusted to 50 mL with ultrapure water. The amount of oxalic acid is measured using an ion chromatograph (IC: Thermo Fisher Scientific, ICS-2000). -By converting it into the amount, the BOB in the non-aqueous electrolyte - The content can be measured. The analytical method using NMR is explained below. The non-aqueous electrolyte is diluted with deuterated DMSO, and LiBF4 is added as a standard substance. 19 F NMR and 11 Measure B NMR of LiPF6 and BOB - The integral ratio of LiBF4 was calculated from the LiPF6 concentration obtained by ion chromatography. - The concentration can be calculated.
[0028] <1-2.FSO3 - , PO2F2 - and B.O.B. - Relationship > FSO3 in non-aqueous electrolyte - Concentration of ([FSO3 - ]), PO2F2 - Concentration of ([PO2F2 - ]) and B.O.B. - Concentration of ([BOB - ]) preferably satisfies the relationship of the following formula (1). [FSO3 - ]>[PO2F2 - ]>[BOB - ] (1) It is more preferable that the relationships of the following formulas (2) and (3) are satisfied. ([FSO3 - ]+[PO2F2 - ]) / ([PO2F2 - ]+[BOB - ])>1.8 (2) [FSO3 - ]<1.3 Mass% (3)
[0029] If the above formula (1) is satisfied, FSO3 - PO2F2 - and B.O.B. -This prevents localized film polymerization and forms a thin and uniform negative electrode film, which makes it easier to achieve the effect of improving the initial output in a low-temperature environment. In addition, when the relationship between the above formulas (2) and (3) is satisfied, the BOB - The increase in film resistance due to FSO3 - and PO2F2 - Since the film derived from the above-mentioned film suppresses the initial output of the battery, the effect of improving the initial output in a low-temperature environment is more easily achieved. As demonstrated in the examples described later, it is particularly preferable that the nonaqueous electrolyte used in the nonaqueous secondary battery of the present invention contains lithium fluorosulfonate (FSO3Li), lithium difluorophosphate (LiPO2F2), and lithium bis(oxalato)borate (LiBOB) in the nonaqueous electrolyte.
[0030] <1-3. Electrolytes> The non-aqueous electrolyte of the present embodiment, like a general non-aqueous electrolyte, usually contains an electrolyte as a component. There is no particular limitation on the electrolyte used in the non-aqueous electrolyte of the present embodiment, and any known electrolyte can be used. Specific examples of the electrolyte will be described in detail below.
[0031] <1-3-1. Lithium salts> As the electrolyte in the non-aqueous electrolyte of this embodiment, a lithium salt is usually used. The lithium salt is not particularly limited as long as it is known to be used for this purpose, and one or more of any lithium salts can be used, and specifically, the following are included. However, the lithium salt in this section does not include the above-mentioned FSO3Li, LiPO2F2, and LiBOB.
[0032] For example, inorganic lithium salts such as LiBF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, LiWF7, etc.; Lithium fluorophosphates such as LiPF6; Lithium tungstate salts such as LiWOF5; Lithium carboxylates such as CF3CO2Li; Lithium sulfonate salts such as CH3SO3Li; Lithium imide salts such as LiN(FSO2)2, LiN(CF3SO2)2; Lithium methide salts such as LiC(FSO2)3; Lithium oxalate salts such as lithium difluorooxalatoborate; Other fluorine-containing organic lithium salts such as LiPF4(CF3)2; etc.
[0033] From the viewpoint of further enhancing the effect of improving the charge / discharge rate characteristics and impedance characteristics, the lithium salt is preferably selected from inorganic lithium salts, lithium fluorophosphate salts, lithium sulfonate salts, lithium imide salts, and lithium oxalate salts.
[0034] The total concentration of these electrolytes in the non-aqueous electrolyte is not particularly limited, but is usually 8% by mass or more, preferably 8.5% by mass or more, more preferably 9% by mass or more, based on the total amount of the non-aqueous electrolyte.The upper limit is usually 18% by mass or less, preferably 17% by mass or less, more preferably 16% by mass or less.When the total concentration of the electrolytes is within the above range, the electrical conductivity is appropriate for the battery operation, so that sufficient output characteristics tend to be obtained.
[0035] <1-4.Non-aqueous solvents> The nonaqueous electrolyte of the present embodiment, like a general nonaqueous electrolyte, usually contains a nonaqueous solvent that dissolves the above-mentioned electrolyte as its main component. There is no particular limitation on the nonaqueous solvent used here, and a known organic solvent can be used. Examples of the organic solvent include saturated cyclic carbonates, chain carbonates, carboxylate esters, ether compounds, and sulfone compounds. Although not particularly limited to these, saturated cyclic carbonates, chain carbonates, and carboxylate esters are preferred, and saturated cyclic carbonates and chain carbonates are more preferred. These can be used alone or in combination of two or more. As a combination of two or more nonaqueous solvents, a combination of two or more selected from the group consisting of saturated cyclic carbonates, chain carbonates, and carboxylate esters is preferred, and a combination of saturated cyclic carbonates or chain carbonates is more preferred.
[0036] <1-4-1. Saturated cyclic carbonates> Examples of the saturated cyclic carbonate include those having an alkylene group having 2 to 4 carbon atoms, and from the viewpoint of improving the battery characteristics resulting from the improvement of the degree of dissociation of lithium ions, saturated cyclic carbonates having 2 to 3 carbon atoms are preferably used. The saturated cyclic carbonate may be a cyclic carbonate having a fluorine atom, such as monofluoroethylene carbonate.
[0037] Examples of the saturated cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Among them, ethylene carbonate and propylene carbonate are preferred, and ethylene carbonate, which is less susceptible to oxidation and reduction, is more preferred. The saturated cyclic carbonate may be used alone or in any combination and ratio of two or more.
[0038] The content of the saturated cyclic carbonate is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but the lower limit of the content when one type is used alone is usually 3% by volume or more, preferably 5% by volume or more, based on the total amount of the solvent in the nonaqueous electrolyte. By setting it in this range, the decrease in electrical conductivity due to the decrease in the dielectric constant of the nonaqueous electrolyte can be avoided, and the large current discharge characteristics, stability to the negative electrode, and cycle characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range. The upper limit is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. By setting it in this range, the oxidation / reduction resistance of the nonaqueous electrolyte tends to be improved, and the stability during high-temperature storage tends to be improved. In the present invention, "volume %" refers to the volume ratio [%] at 25° C. and 1 atmospheric pressure.
[0039] <1-4-2. Chain carbonate> As the chain carbonate, one having 3 to 7 carbon atoms is usually used, and in order to adjust the viscosity of the electrolyte solution within an appropriate range, a chain carbonate having 3 to 5 carbon atoms is preferably used.
[0040] Specific examples of chain carbonates include dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, methyl-n-propyl carbonate, n-butyl methyl carbonate, isobutyl methyl carbonate, t-butyl methyl carbonate, ethyl-n-propyl carbonate, n-butyl ethyl carbonate, isobutyl ethyl carbonate, and t-butyl ethyl carbonate.
[0041] Of these, dimethyl carbonate, diethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, ethyl methyl carbonate, and methyl-n-propyl carbonate are preferred, and dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate are particularly preferred.
[0042] In addition, chain carbonates having fluorine atoms (hereinafter, sometimes abbreviated as "fluorinated chain carbonate") can also be suitably used. The number of fluorine atoms in the fluorinated chain carbonate is not particularly limited as long as it is 1 or more, but is usually 6 or less, and preferably 4 or less. When the fluorinated chain carbonate has multiple fluorine atoms, they may be bonded to the same carbon or different carbons. Examples of the fluorinated chain carbonate include fluorinated dimethyl carbonate derivatives, fluorinated ethyl methyl carbonate derivatives, and fluorinated diethyl carbonate derivatives.
[0043] Examples of the fluorinated dimethyl carbonate derivative include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, bis(fluoromethyl)carbonate, bis(difluoro)methyl carbonate, and bis(trifluoromethyl)carbonate.
[0044] Examples of fluorinated ethyl methyl carbonate derivatives include 2-fluoroethyl methyl carbonate, ethyl fluoromethyl carbonate, 2,2-difluoroethyl methyl carbonate, 2-fluoroethyl fluoromethyl carbonate, ethyl difluoromethyl carbonate, 2,2,2-trifluoroethyl methyl carbonate, 2,2-difluoroethyl fluoromethyl carbonate, 2-fluoroethyl difluoromethyl carbonate, and ethyl trifluoromethyl carbonate.
[0045] Examples of fluorinated diethyl carbonate derivatives include ethyl-(2-fluoroethyl)carbonate, ethyl-(2,2-difluoroethyl)carbonate, bis(2-fluoroethyl)carbonate, ethyl-(2,2,2-trifluoroethyl)carbonate, 2,2-difluoroethyl-2'-fluoroethyl carbonate, bis(2,2-difluoroethyl)carbonate, 2,2,2-trifluoroethyl-2'-fluoroethyl carbonate, 2,2,2-trifluoroethyl-2',2'-difluoroethyl carbonate, and bis(2,2,2-trifluoroethyl)carbonate.
[0046] The chain carbonate may be used alone or as a mixture of two or more kinds in any combination and in any ratio.
[0047] The content of the chain carbonate is not particularly limited, but is usually 15% by volume or more, preferably 20% by volume or more, more preferably 25% by volume or more, based on the total amount of the solvent in the nonaqueous electrolyte. Also, it is usually 90% by volume or less, preferably 85% by volume or less, more preferably 80% by volume or less. By setting the content of the chain carbonate within the above range, the viscosity of the nonaqueous electrolyte can be set to an appropriate range, the decrease in ion conductivity can be suppressed, and the output characteristics of the nonaqueous electrolyte secondary battery can be easily set to a good range. When two or more types of chain carbonates are used in combination, the total amount of the chain carbonates can be set to satisfy the above range.
[0048] Furthermore, by combining a specific chain carbonate with ethylene carbonate in a specific content, the battery performance can be significantly improved.
[0049] For example, when dimethyl carbonate and ethyl methyl carbonate are selected as specific chain carbonates, the content of ethylene carbonate is not particularly limited and is arbitrary as long as it does not significantly impair the effects of the present invention, but it is usually 15% by volume or more, preferably 20% by volume, and usually 45% by volume or less, preferably 40% by volume or less, based on the total amount of the solvent in the non-aqueous electrolyte solution, the content of dimethyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less, based on the total amount of the solvent in the non-aqueous electrolyte solution, and the content of ethyl methyl carbonate is usually 20% by volume or more, preferably 30% by volume or more, and usually 50% by volume or less, preferably 45% by volume or less. By setting the content within the above range, there is a tendency that high temperature stability is excellent and gas generation is suppressed.
[0050] <1-4-3. Ether compounds> As the ether-based compound, a chain ether having 3 to 10 carbon atoms and a cyclic ether having 3 to 6 carbon atoms are preferred.
[0051] The ether-based compounds may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The content of the ether-based compound is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but is usually 1% by volume or more, preferably 2% by volume or more, more preferably 3% by volume or more, and usually 30% by volume or less, preferably 25% by volume or less, more preferably 20% by volume or less, in 100% by volume of the non-aqueous solvent. When two or more ether-based compounds are used in combination, the total amount of the ether-based compounds should satisfy the above range. If the content of the ether-based compound is within the above preferred range, it is easy to ensure the effect of improving the lithium ion dissociation degree of the chain ether and improving the ion conductivity due to the viscosity reduction. In addition, when the negative electrode active material is a carbonaceous material, the phenomenon in which the chain ether is co-inserted with the lithium ion can be suppressed, so that the input / output characteristics and the charge / discharge rate characteristics can be set to an appropriate range.
[0052] <1-4-4. Sulfone compounds> The sulfone compound is not particularly limited, whether it is a cyclic sulfone or a chain sulfone, but in the case of a cyclic sulfone, the carbon number is usually 3 to 6, preferably 3 to 5, and in the case of a chain sulfone, the carbon number is usually 2 to 6, preferably 2 to 5. The number of sulfonyl groups in one molecule of the sulfone compound is not particularly limited, but is usually 1 or 2.
[0053] Examples of cyclic sulfones include monosulfone compounds such as trimethylene sulfones, tetramethylene sulfones, and hexamethylene sulfones; and disulfone compounds such as trimethylene disulfones, tetramethylene disulfones, and hexamethylene disulfones. Among these, from the viewpoint of dielectric constant and viscosity, tetramethylene sulfones, tetramethylene disulfones, hexamethylene sulfones, and hexamethylene disulfones are more preferred, and tetramethylene sulfones (sulfolanes) are particularly preferred.
[0054] The sulfolane is preferably sulfolane and / or a sulfolane derivative (hereinafter, sulfolane may be abbreviated as "sulfolane") The sulfolane derivative is preferably one in which one or more hydrogen atoms bonded to the carbon atom constituting the sulfolane ring are substituted with a fluorine atom or an alkyl group.
[0055] The sulfone-based compounds may be used alone or as a mixture of two or more kinds in any combination and in any ratio. The content of the sulfone-based compound is not particularly limited, and is arbitrary as long as it does not significantly impair the effects of the present invention, but is usually 0.3% by volume or more, preferably 0.5% by volume or more, more preferably 1% by volume or more, and is usually 40% by volume or less, preferably 35% by volume or less, more preferably 30% by volume or less, based on the total amount of the solvent in the non-aqueous electrolyte. When two or more sulfone-based compounds are used in combination, the total amount of the sulfone-based compounds should be set to satisfy the above range. If the content of the sulfone-based compound is within the above range, an electrolyte with excellent high-temperature storage stability tends to be obtained.
[0056] <1-4-5. Carboxylic acid esters> The carboxylate is preferably a chain carboxylate, more preferably a saturated chain carboxylate. The total number of carbon atoms in the carboxylate is usually 3 to 7, and from the viewpoint of improving the battery characteristics resulting from the improvement of the output characteristics, a carboxylate having 3 to 5 carbon atoms is preferably used.
[0057] Examples of the carboxylate include saturated chain carboxylates such as methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl pivalate, and ethyl pivalate, and unsaturated chain carboxylates such as methyl acrylate, ethyl acrylate, methyl methacrylate, and ethyl methacrylate. Among them, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, methyl pivalate, and ethyl pivalate are preferred, and from the viewpoint of improving output characteristics, methyl acetate, ethyl acetate, methyl propionate, and ethyl propionate are more preferred. The carboxylate may be used alone or in any combination and ratio of two or more.
[0058] The content of the carboxylate is not particularly limited and may be any content as long as it does not significantly impair the effects of the present invention, but the lower limit is usually 3% by volume or more, preferably 5% by volume or more, based on the total amount of the solvent in the nonaqueous electrolyte. By setting the content in this range, the decrease in electrical conductivity due to the decrease in the dielectric constant of the nonaqueous electrolyte can be avoided, and the large current discharge characteristics, stability to the negative electrode, and cycle characteristics of the nonaqueous electrolyte secondary battery can be easily set in a good range. The upper limit is usually 90% by volume or less, preferably 85% by volume or less, and more preferably 80% by volume or less. By setting the content in this range, the oxidation / reduction resistance of the nonaqueous electrolyte tends to be improved, and the stability during high-temperature storage tends to be improved. In the present invention, the volume % means the volume at 25° C. and 1 atmospheric pressure.
[0059] <1-5. Other fluorosulfonates> There are no particular limitations on the counter ion of the fluorosulfonate ion contained in other fluorosulfonates, but <1-1-1. Fluorosulfonate ion (FSO3 - )> Cations other than those listed in the above, including rubidium, cesium, barium, and NR 13 R 14 R 15 R 16 (In the formula, R 13 ~R 16 Each of the groups independently represents a hydrogen atom or an organic group having 1 to 12 carbon atoms. Examples of the ammonium group include ammonium represented by the following formula: - includes fluorosulfonate ions constituting other fluorosulfonate salts.
[0060] Other specific examples of fluorosulfonates include: Examples of the fluorosulfonate include rubidium fluorosulfonate and cesium fluorosulfonate.
[0061] The other fluorosulfonates may be used alone or in any combination and ratio of two or more. - The total content of cations contained in FSO3 and other fluorosulfonates is usually 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and usually 15% by mass or less, preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 3% by mass or less, especially preferably 2% by mass or less, and particularly preferably 1% by mass or less, in 100% by mass of the non-aqueous electrolyte. - and the other cations contained in the fluorosulfonate salt so as to satisfy the above range. Within this range, swelling of the nonaqueous electrolyte secondary battery due to charging and discharging can be suitably suppressed.
[0062] <1-6. Auxiliaries> The nonaqueous electrolyte solution of the present embodiment may contain the following auxiliary agents within the range in which the effects of the present invention are achieved. Unsaturated cyclic carbonates such as vinylene carbonate, vinyl ethylene carbonate, or ethynyl ethylene carbonate; Carbonate compounds such as methoxyethyl-methyl carbonate; Spiro compounds such as methyl-2-propynyl oxalate; Sulfur-containing compounds such as ethylene sulfite; Isocyanate compounds such as diisocyanates having a cycloalkylene group, such as 1,3-bis(isocyanatomethyl)cyclohexane; Nitrogen-containing compounds such as 1-methyl-2-pyrrolidinone; Hydrocarbon compounds such as cycloheptane; Fluorinated aromatic compounds such as fluorobenzene; Silane compounds such as tris(trimethylsilyl) borate; 2-(methanesulfonyloxy)propionic acid 2-propynyl ester compounds; Lithium salts such as lithium ethylmethyloxycarbonylphosphonate; Isocyanate esters such as triallyl isocyanurate; These may be used alone or in combination of two or more. By adding these auxiliary agents, the capacity retention characteristics and cycle characteristics after high-temperature storage can be improved.
[0063] The content of the other auxiliary agent is not particularly limited, and is arbitrary as long as it does not significantly impair the effect of the present invention. The content of the other auxiliary agent is usually 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 0.2 mass% or more, and is usually 5 mass% or less, preferably 3 mass% or less, more preferably 1 mass% or less, based on the total amount of the non-aqueous electrolyte. Within this range, the effect of the other auxiliary agent is easily exerted, and high-temperature storage stability tends to be improved. When two or more kinds of other auxiliary agents are used in combination, the total amount of the other auxiliary agents should be set to satisfy the above range.
[0064] In this specification, the composition of the nonaqueous electrolyte means the composition at the time of shipping the battery into which the nonaqueous electrolyte is injected. However, it is not necessary to analyze the composition of the nonaqueous electrolyte at the time of shipping, and the battery may be manufactured so that the composition at the time of shipping falls within a desired range by measuring the contents of the components during the production of the nonaqueous electrolyte or during injection of the nonaqueous electrolyte into the battery. That is, the nonaqueous electrolyte may be mixed so that the ratio of each component is a predetermined composition when preparing the nonaqueous electrolyte. After preparing the nonaqueous electrolyte, the nonaqueous electrolyte itself can be subjected to analysis to confirm the composition. The nonaqueous electrolyte may be collected from the completed nonaqueous electrolyte secondary battery and subjected to analysis. Examples of a method for collecting the nonaqueous electrolyte include a method in which the battery container is partially or entirely opened or a hole is provided in the battery container to collect the electrolyte. The opened battery container may be centrifuged to collect the electrolyte, or an extraction solvent (for example, acetonitrile dehydrated to a water content of 10 ppm or less is preferable) may be placed in the opened battery container or the extraction solvent may be brought into contact with the battery element to extract the electrolyte. The nonaqueous electrolyte collected by such a method can be subjected to analysis. The collected nonaqueous electrolyte may be diluted to provide conditions suitable for analysis and subjected to analysis.
[0065] The optimal method for analyzing a non-aqueous electrolyte solution varies depending on the type of composition of the non-aqueous electrolyte solution, but specific examples include inductively coupled plasma (ICP) emission spectroscopy, nuclear magnetic resonance (hereinafter sometimes abbreviated as NMR), gas chromatography, ion chromatography, and other liquid chromatography. The NMR analysis method will be described below. In an inert atmosphere, the non-aqueous electrolyte solution is dissolved in a deuterated solvent that has been dehydrated to 10 ppm or less, and then placed in an NMR tube to perform NMR measurement. Alternatively, a double tube may be used as the NMR tube, with the non-aqueous electrolyte solution placed in one tube and the deuterated solvent placed in the other tube to perform NMR measurement. Examples of deuterated solvents include deuterated acetonitrile and deuterated dimethyl sulfoxide. When determining the concentration of the components of the non-aqueous electrolyte solution, a specified amount of a standard substance is dissolved in the deuterated solvent, and the concentration of each component can be calculated from the ratio of the spectra. Alternatively, the concentration of one or more components constituting the non-aqueous electrolyte solution can be determined in advance by another analytical method such as gas chromatography, and the concentration can be calculated from the spectral ratio of the component with a known concentration to the other components. The nuclear magnetic resonance analyzer used is preferably one with a proton resonance frequency of 400 MHz or more. 1 H, 31 P, 19 F, 11 Examples include B. These analytical techniques may be used alone or in combination of two or more.
[0066] <2. Non-aqueous electrolyte secondary battery> A nonaqueous electrolyte secondary battery according to one embodiment of the present invention is a nonaqueous electrolyte secondary battery comprising a positive electrode and a negative electrode capable of absorbing and releasing metal ions, and a nonaqueous electrolyte according to the above-mentioned embodiment of the present invention. More specifically, the battery comprises a positive electrode having a current collector and a positive electrode active material layer provided on the current collector, a negative electrode having a current collector and a negative electrode active material layer provided on the current collector and capable of absorbing and releasing metal ions, and a nonaqueous electrolyte.
[0067] <2-1. Battery configuration> The nonaqueous electrolyte secondary battery of this embodiment is the same as the conventional nonaqueous electrolyte secondary battery except for the nonaqueous electrolyte. Usually, the positive electrode and the negative electrode are laminated through a porous membrane (separator) impregnated with the nonaqueous electrolyte, and these are housed in a case (exterior body). Therefore, the shape of the nonaqueous electrolyte secondary battery of this embodiment is not particularly limited, and may be any of a cylindrical type, a square type, a laminate type, a coin type, a large type, etc.
[0068] <2-2. Non-aqueous electrolyte> As the non-aqueous electrolyte solution, the non-aqueous electrolyte solution according to the embodiment of the present invention is used. Note that, within the scope of the present invention, it is also possible to mix other non-aqueous electrolyte solutions with the non-aqueous electrolyte solution.
[0069] <2-3. Positive electrode> In one embodiment of the present invention, the positive electrode has a current collector and a positive electrode active material layer provided on the current collector. The positive electrode used in the nonaqueous electrolyte secondary battery of this embodiment will be described in detail below.
[0070] <2-3-1. Positive electrode active material> The positive electrode active material used in the positive electrode will be described below. (1) Composition The positive electrode active material is not particularly limited as long as it can electrochemically absorb and release metal ions, but for example, it is preferable that it is capable of electrochemically absorbing and releasing lithium ions, and it is preferable that it contains at least one selected from the group consisting of lithium-cobalt composite oxide, lithium-cobalt-nickel composite oxide, lithium-manganese composite oxide, lithium-cobalt-manganese composite oxide, lithium-nickel composite oxide, lithium-nickel-manganese composite oxide, and lithium-cobalt-nickel-manganese composite oxide. This is because the transition metals contained in these composite oxides have redox potentials suitable for use as positive electrode materials for secondary batteries and are suitable for high capacity applications.
[0071] The transition metal component of the composite oxide (also called lithium transition metal oxide) may include Ni, Co and / or Mn, but other metals include V, Ti, Cr, Fe, Cu, Al, Mg, Zr, Er, etc., with Ti, Fe, Al, Mg, Zr, etc. being preferred. Specific examples of lithium transition metal oxides include LiCoO2, LiNi 0.85 Co 0.10 Al 0.05 O2, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.33 Co 0.33 Mn 0.33 O2, Li 1.05 Ni 0.33 Mn 0.33 Co 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, Li 1.05 Ni 0.50 Mn 0.29 Co 0.21 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiMn2O4, LiMn 1.8 Al 0.2 O4, LiMn 1.5 Ni 0.5 Examples include O4.
[0072] In addition, two or more of the above positive electrode active materials may be mixed and used. Similarly, at least one of the above positive electrode active materials may be mixed and used with another positive electrode active material. Examples of the other positive electrode active materials include transition metal oxides, transition metal phosphate compounds, transition metal silicate compounds, and transition metal borate compounds not listed above. In addition, the transition metal of the lithium-containing transition metal phosphate compound is preferably V, Ti, Cr, Mn, Fe, Co, Ni, Cu, etc., and specific examples include iron phosphates such as LiFePO4, Li3Fe2(PO4)3, LiFeP2O7, cobalt phosphates such as LiCoPO4, manganese phosphates such as LiMnPO4, and lithium transition metal phosphate compounds in which a part of the transition metal atoms that constitute the main part of these lithium transition metal phosphate compounds has been replaced with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Nb, Mo, Sn, W, etc. Among them, lithium iron phosphate compounds are preferred because iron is an abundant and extremely inexpensive metal and is less harmful. That is, among the above specific examples, LiFePO4 can be cited as a more preferred specific example.
[0073] (2) Surface coating The above-mentioned positive electrode active material may have a surface to which a substance (hereinafter, appropriately referred to as a "surface-attached substance") having a different composition from the substance constituting the main positive electrode active material is attached. Examples of the surface-attached substance include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide, sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate, carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate, and carbon.
[0074] These surface-attaching substances can be attached to the surface of the positive electrode active material by, for example, a method of dissolving or suspending the substance in a solvent, impregnating the positive electrode active material with the substance, and then drying the substance, a method of dissolving or suspending a surface-attaching substance precursor in a solvent, impregnating the positive electrode active material with the substance, and then reacting the substance by heating or the like, a method of adding the substance to a positive electrode active material precursor and simultaneously baking the substance, etc. When carbon is attached, a method of mechanically attaching the carbonaceous material, for example, in the form of activated carbon, etc., after the surface-attaching substance is attached can also be used.
[0075] The mass of the surface-attached substance attached to the surface of the positive electrode active material is preferably 0.1 ppm or more, more preferably 1 ppm or more, and even more preferably 10 ppm or more, relative to the mass of the positive electrode active material, and is preferably 20% or less, more preferably 10% or less, and even more preferably 5% or less. The surface-attached substance can suppress the oxidation reaction of the non-aqueous electrolyte on the surface of the positive electrode active material, thereby improving the battery life. In addition, when the amount of the attached substance is within the above range, the effect can be fully exerted, and the inflow and outflow of lithium ions is not hindered, and the resistance is not likely to increase.
[0076] (3) Shape The positive electrode active material particles may have a conventional shape such as a block, polyhedron, sphere, oval sphere, plate, needle, column, etc. Primary particles may be aggregated to form secondary particles, and the secondary particles may have a spherical or oval sphere shape.
[0077] (4) Manufacturing method of positive electrode active material The method for producing the positive electrode active material is not particularly limited as long as it does not deviate from the gist of the present invention. Several methods can be mentioned, and a general method for producing an inorganic compound can be used. In particular, various methods can be considered for producing spherical or ellipsoidal active materials. One example is a method in which transition metal raw materials such as transition metal nitrates or sulfates, and raw materials of other elements as necessary, are dissolved or pulverized and dispersed in a solvent such as water, and the pH is adjusted while stirring to produce and recover a spherical precursor, which is then dried as necessary, and a Li source such as LiOH, Li2CO3, or LiNO3 is added and the mixture is fired at high temperature to obtain the active material.
[0078] Another example of the method is to dissolve or pulverize and disperse transition metal raw materials such as transition metal nitrates, sulfates, hydroxides, and oxides, and, if necessary, raw materials of other elements, in a solvent such as water, and then dry and mold the resulting mixture using a spray dryer or the like to form a spherical or ellipsoidal precursor. To this, a Li source such as LiOH, Li2CO3, or LiNO3 is added, and the mixture is fired at high temperature to obtain an active material.
[0079] As yet another example of the method, a transition metal raw material such as a transition metal nitrate, sulfate, hydroxide, or oxide, a Li source such as LiOH, Li2CO3, or LiNO3, and, if necessary, raw materials of other elements are dissolved or pulverized and dispersed in a solvent such as water, and then dried and molded using a spray dryer or the like to form a spherical or ellipsoidal precursor, which is then fired at a high temperature to obtain the active material.
[0080] <2-3-2. Positive electrode structure and manufacturing method> The configuration of the positive electrode used in this embodiment and the method for producing the same will be described below. (Method of making positive electrode) The positive electrode is produced by forming a positive electrode active material layer containing positive electrode active material particles and a binder on a current collector. The positive electrode using the positive electrode active material can be produced by any known method. For example, the positive electrode active material and the binder, and if necessary, a conductive material and a thickener, etc. are mixed in a dry state to form a sheet, which is then pressed onto the positive electrode current collector, or these materials are dissolved or dispersed in a liquid medium to form a slurry, which is then applied to the positive electrode current collector and dried to form a positive electrode active material layer on the current collector, thereby obtaining a positive electrode.
[0081] The content of the positive electrode active material in the positive electrode active material layer is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and preferably 99.9% by mass or less, more preferably 99% by mass or less. When the content of the positive electrode active material is within the above range, the electric capacity can be sufficiently secured. Furthermore, the strength of the positive electrode is also sufficient. In addition, the positive electrode active material powder in the present invention may be used alone, or two or more types having different compositions or different powder properties may be used in any combination and ratio. When two or more types of active materials are used in combination, it is preferable to use the composite oxide containing lithium and manganese as a component of the powder. Cobalt or nickel is an expensive metal with a small amount of resources, and the amount of active material used is large in large batteries that require high capacity for automobiles, etc., which is not preferable from the viewpoint of cost, so it is desirable to use manganese as a cheaper transition metal as the main component.
[0082] <2-4. Negative electrode> The negative electrode active material used in the negative electrode will be described below. There are no particular limitations on the negative electrode active material as long as it is capable of electrochemically absorbing and releasing metal ions. Specific examples include carbonaceous materials and other materials having carbon as a constituent element, alloy-based materials, and the like. These materials may be used alone or in any combination of two or more.
[0083] <2-4-1. Negative electrode active material> As mentioned above, examples of the negative electrode active material include carbonaceous materials and alloy-based materials. Examples of the carbonaceous material include (1) natural graphite, (2) artificial graphite, (3) amorphous carbon, (4) carbon-coated graphite, (5) graphite-coated graphite, and (6) resin-coated graphite.
[0084] (1) Examples of natural graphite include scaly graphite, scaly graphite, soil graphite, and / or graphite particles obtained by subjecting these graphites to treatments such as spheroidization and densification. Among these, from the viewpoints of particle packing and charge / discharge rate characteristics, spherical or ellipsoidal graphite that has been subjected to a spheroidization treatment is particularly preferred.
[0085] The spheronization treatment can be carried out using a device that repeatedly applies mechanical actions to particles, such as compression, friction, shear force, and particle interactions, mainly impact force.
[0086] Specifically, a device having a rotor with many blades installed inside a casing, which rotates at high speed to apply mechanical actions such as impact compression, friction, shear force, etc. to the (1) natural graphite raw material introduced inside, thereby carrying out spheroidization is preferable. Also, a device having a mechanism for repeatedly applying mechanical actions by circulating the raw material is preferable.
[0087] For example, when the spheronization treatment is performed using the above-mentioned device, the peripheral speed of the rotating rotor is preferably set to 30 to 100 m / sec, more preferably 40 to 100 m / sec, and even more preferably 50 to 100 m / sec. Although the spheronization treatment can be performed by simply passing the raw material through the device, it is preferable to circulate or retain the raw material in the device for 30 seconds or more, and more preferably to circulate or retain the raw material in the device for 1 minute or more.
[0088] (2) Examples of artificial graphite include those produced by graphitizing organic compounds such as coal tar pitch, coal-based heavy oil, atmospheric residual oil, petroleum-based heavy oil, aromatic hydrocarbons, nitrogen-containing cyclic compounds, sulfur-containing cyclic compounds, polyphenylene, polyvinyl chloride, polyvinyl alcohol, polyacrylonitrile, polyvinyl butyral, natural polymers, polyphenylene silicide, polyphenylene oxide, furfuryl alcohol resin, phenol-formaldehyde resin, and imide resin at a temperature usually in the range of 2500°C or higher and usually 3200°C or lower, and then pulverizing and / or classifying as necessary.
[0089] In this case, a silicon-containing compound or a boron-containing compound can be used as a graphitization catalyst. In addition, an artificial graphite obtained by graphitizing mesocarbon microbeads separated during the heat treatment of pitch can be used. Furthermore, an artificial graphite of granulated particles consisting of primary particles can be used. For example, mesocarbon microbeads and graphite particles obtained by mixing graphitizable carbonaceous material powder such as coke with a graphitizable binder such as tar or pitch and a graphitization catalyst, graphitizing the mixture, and pulverizing the mixture as necessary can be used. The graphite particles are obtained by assembling or bonding a plurality of flat particles so that the oriented planes are non-parallel.
[0090] (3) Examples of amorphous carbon include amorphous carbon particles obtained by using graphitizable carbon precursors such as tar and pitch as raw materials and heat-treating them at least once in a temperature range in which graphitization does not occur (400 to 2200°C), and amorphous carbon particles obtained by using non-graphitizable carbon precursors such as resin as raw materials and heat-treating them.
[0091] (4) Carbon-coated graphite can be obtained as follows. Natural graphite and / or artificial graphite are mixed with a carbon precursor, which is an organic compound such as tar, pitch, or resin, and the mixture is heat-treated at least once in the range of 400 to 2300°C. The obtained natural graphite and / or artificial graphite is used as core graphite, which is then coated with amorphous carbon to obtain a carbon-graphite composite. This carbon-graphite composite can be referred to as carbon-coated graphite (4).
[0092] The composite may be in the form of a core graphite whose surface is entirely or partially covered with amorphous carbon, or a plurality of primary particles may be composited with carbon originating from the carbon precursor as a binder. The carbon-graphite composite may also be obtained by reacting natural graphite and / or artificial graphite with a hydrocarbon gas such as benzene, toluene, methane, propane, or aromatic volatile matter at high temperature to deposit carbon on the graphite surface (CVD).
[0093] (5) Graphite-coated graphite can be obtained as follows: Natural graphite and / or artificial graphite are mixed with a carbon precursor of an easily graphitizable organic compound such as tar, pitch, or resin, and the mixture is heat-treated at least once in the range of about 2400 to 3200° C. The obtained natural graphite and / or artificial graphite is used as core graphite, and the entire or part of the surface of the core graphite is coated with a graphitized material to obtain graphite-coated graphite (5).
[0094] (6) Resin-coated graphite can be obtained, for example, by mixing natural graphite and / or artificial graphite with a resin or the like, drying the mixture at a temperature of less than 400°C to obtain natural graphite and / or artificial graphite as core graphite, and then coating the core graphite with a resin or the like.
[0095] Moreover, the carbonaceous materials (1) to (6) explained above may be used alone or as a mixture of two or more kinds in any combination and ratio.
[0096] Examples of organic compounds such as tar, pitch, and resins used in the carbonaceous materials (2) to (5) above include coal-based heavy oil, direct current heavy oil, cracked petroleum heavy oil, aromatic hydrocarbons, N-ring compounds, S-ring compounds, polyphenylene, organic synthetic polymers, natural polymers, thermoplastic resins, and thermosetting resins that can be carbonized. The raw organic compounds may be dissolved in a low molecular weight organic solvent to adjust the viscosity during mixing.
[0097] As the natural graphite and / or artificial graphite that is the raw material for the core graphite, natural graphite that has been subjected to a spheroidizing treatment is preferred.
[0098] Next, as long as the alloy-based material used as the negative electrode active material can occlude and release lithium, it may be any of lithium metal, simple metals and alloys that form lithium alloys, or compounds such as their oxides, carbides, nitrides, silicides, sulfides or phosphides, and is not particularly limited. The simple metals and alloys that form lithium alloys are preferably materials containing group 13 and group 14 metal and metalloid elements (i.e., excluding carbon), more preferably simple metals of aluminum, silicon and tin, and alloys or compounds containing these atoms, and still more preferably those having silicon or tin as a constituent element, such as simple metals of silicon and tin, and alloys or compounds containing these atoms. These may be used alone, or two or more of them may be used in combination at any combination and ratio.
[0099] <Metal particles capable of alloying with Li> When using a simple metal and alloy that form a lithium alloy, or a compound such as their oxide, carbide, nitride, silicide, sulfide or phosphide as the negative electrode active material, the metal capable of alloying with Li is in particle form. As a method for confirming that the metal particles are metal particles capable of alloying with Li, identification of the metal particle phase by X-ray diffraction, observation and elemental analysis of the particle structure by an electron microscope, elemental analysis by X-ray fluorescence, etc. can be mentioned.
[0100] As the metal particles capable of alloying with Li, any conventionally known ones can be used. However, from the viewpoints of the capacity and cycle life of the non-aqueous electrolyte secondary battery, the metal particles are preferably, for example, a metal or its compound selected from the group consisting of Fe, Co, Sb, Bi, Pb, Ni, Ag, Si, Sn, Al, Zr, Cr, P, S, V, Mn, As, Nb, Mo, Cu, Zn, Ge, In, Ti and W. Also, an alloy composed of two or more metals may be used, or the metal particles may be alloy particles formed of two or more metal elements. Among these, a metal or its metal compound selected from the group consisting of Si, Sn, As, Sb, Al, Zn and W is preferable.
[0101] Examples of the metal compound include metal oxides, metal nitrides, metal carbides, etc. An alloy composed of two or more metals may also be used.
[0102] Among the metal particles capable of alloying with Li, Si or Si metal compound is preferable. The Si metal compound is preferably a Si metal oxide. Si or Si metal compound is preferable in terms of increasing the capacity of the battery. In this specification, Si or Si metal compound is collectively referred to as Si compound. Specifically, examples of the Si compound include SiO x , SiN x , SiC x , SiZ x O y (Z = C, N), etc. The Si compound is preferably a Si metal oxide, and the Si metal oxide is represented by the general formula SiO x . This general formula SiO x is obtained using silicon dioxide (SiO2) and metallic silicon (Si) as raw materials, and the value of x is usually 0 ≦ x < 2. SiO x has a larger theoretical capacity compared to graphite, and furthermore, amorphous Si or nano-sized Si crystals allow easy entry and exit of alkali ions such as lithium ions, making it possible to obtain a high capacity.
[0103] Specifically, the Si metal oxide is represented by SiO x , where x is 0 ≦ x < 2, more preferably 0.2 or more and 1.8 or less, still more preferably 0.4 or more and 1.6 or less, and particularly preferably 0.6 or more and 1.4 or less. Within this range, the battery has a high capacity and at the same time, it is possible to reduce the irreversible capacity due to the bond between Li and oxygen.
[0104] <Oxygen content of metal particles capable of alloying with Li> The oxygen content of the metal particles capable of alloying with Li is not particularly limited, but is usually 0.01% by mass or more and 8% by mass or less, preferably 0.05% by mass or more and 5% by mass or less. The oxygen distribution state within the particles may be present near the surface, within the particles, or uniformly within the particles, but is particularly preferably present near the surface. When the oxygen content of the metal particles capable of alloying with Li is within the above range, the volume expansion associated with the charge and discharge of the non-aqueous electrolyte secondary battery is suppressed due to the strong bond between the metal particles and O (oxygen atoms), and the cycle characteristics are excellent, which is preferable.
[0105] <Negative electrode active material containing metal particles capable of alloying with Li and graphite particles> The negative electrode active material may contain metal particles capable of alloying with Li and graphite particles. The negative electrode active material may be a mixture in which the metal particles capable of alloying with Li and the graphite particles are mixed in a state of mutually independent particles, or a composite in which the metal particles capable of alloying with Li are present on the surface and / or inside of the graphite particles.
[0106] The composite of metal particles capable of alloying with Li and graphite particles (also referred to as composite particles) is not particularly limited as long as it contains metal particles capable of alloying with Li and graphite particles. Preferably, it is a particle in which metal particles capable of alloying with Li and graphite particles are integrated by physical and / or chemical bonds. A more preferable form is that the metal particles capable of alloying with Li and the graphite particles are in a state where each solid component is dispersed in the particle to the extent that they are present in at least both the surface and the bulk interior of the composite particle, and in a form where graphite particles are present in order to integrate them by physical and / or chemical bonds. A more specific preferable form is a composite material composed of at least metal particles capable of alloying with Li and graphite particles, and a composite material (negative electrode active material) characterized in that metal particles capable of alloying with Li are present in the gaps within the structure of particles having a folded structure with curved surfaces, preferably natural graphite. Further, the gaps may be voids, or substances such as amorphous carbon, graphite-like substances, resins, etc. that buffer the expansion and contraction of metal particles capable of alloying with Li may be present in the gaps.
[0107] <Content ratio of metal particles capable of alloying with Li> The content ratio of metal particles capable of alloying with Li to the total of metal particles capable of alloying with Li and graphite particles is usually 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1.0% by mass or more, still more preferably 2.0% by mass or more. Also, it is usually 99% by mass or less, preferably 50% by mass or less, more preferably 40% by mass or less, still more preferably 30% by mass or less, even more preferably 25% by mass or less, even more preferably 20% by mass or less, particularly preferably 15% by mass or less, and most preferably 10% by mass or less. Being within this range is preferable in that it enables control of side reactions on the Si surface and makes it possible to obtain sufficient capacity in a non-aqueous electrolyte secondary battery.
[0108] <Coating rate> In this embodiment, the negative electrode active material may be coated with a carbonaceous material or a graphite material. Among these, it is preferable to coat with an amorphous carbonaceous material from the viewpoint of lithium ion acceptance. The coating rate is usually 0.5% to 30%, preferably 1% to 25%, more preferably 2% to 20%. The upper limit of the coating rate is preferably within the above range from the viewpoint of reversible capacity when assembled into a battery, and the lower limit of the coating rate is preferably within the above range from the viewpoint of the core carbonaceous material being uniformly coated with amorphous carbon to be firmly granulated, and from the viewpoint of the particle size of the particles obtained when pulverized after firing.
[0109] The coverage (content) of the organic compound-derived carbonized material in the final negative electrode active material can be calculated by the following formula using the amount of the negative electrode active material, the amount of the organic compound, and the carbon residue rate measured by a micro method in accordance with JIS K 2270. Formula: Coverage rate of carbon derived from organic compound (%) = (mass of organic compound × carbon remaining rate × 100) / {mass of negative electrode active material + (mass of organic compound × carbon remaining rate)}
[0110] <Internal porosity> The internal porosity of the negative electrode active material is usually 1% or more, preferably 3% or more, more preferably 5% or more, and even more preferably 7% or more. It is usually less than 50%, preferably 40% or less, more preferably 30% or less, and even more preferably 20% or less. If the internal porosity is too small, the amount of liquid in the particles of the negative electrode active material in a nonaqueous electrolyte secondary battery tends to be small. On the other hand, if the internal porosity is too large, the gaps between the particles tend to be small when the material is used as an electrode. The lower limit of the internal porosity is preferably set to the above range from the viewpoint of charge / discharge characteristics, and the upper limit is preferably set to the above range from the viewpoint of diffusion of the nonaqueous electrolyte. In addition, as described above, the gap may be a void, or a substance that buffers the expansion and contraction of the metal particles that can be alloyed with Li, such as amorphous carbon, graphite, or resin, may be present in the gap or the gap may be filled with these substances.
[0111] <2-4-2. Negative electrode structure and manufacturing method> The negative electrode can be manufactured by any known method as long as it does not significantly impair the effects of the present invention. For example, the negative electrode can be formed by adding a binder, a solvent, and, if necessary, a thickener, a conductive material, a filler, etc. to the negative electrode active material to form a slurry, applying the slurry to a current collector, drying it, and pressing it.
[0112] In addition, the alloy-based material negative electrode can be manufactured by any known method. Specifically, the manufacturing method of the negative electrode includes, for example, a method of adding a binder, a conductive material, etc. to the above-mentioned negative electrode active material, and then rolling the material to form a sheet electrode, or a method of compressing the material to form a pellet electrode. Usually, a method of forming a thin film layer (negative electrode active material layer) containing the above-mentioned negative electrode active material on a current collector for a negative electrode (hereinafter sometimes referred to as "negative electrode current collector") by a coating method, a vapor deposition method, a sputtering method, a plating method, or the like is used. In this case, a binder, a thickener, a conductive material, a solvent, etc. are added to the above-mentioned negative electrode active material to form a slurry, which is applied to a negative electrode current collector, dried, and then pressed to densify, thereby forming a negative electrode active material layer on the negative electrode current collector.
[0113] Examples of the material for the negative electrode current collector include steel, copper, copper alloy, nickel, nickel alloy, stainless steel, etc. Among these, copper foil is preferred from the viewpoints of ease of processing into a thin film and cost.
[0114] The thickness of the negative electrode current collector is usually 1 μm or more, preferably 5 μm or more, and usually 100 μm or less, preferably 50 μm or less. If the thickness of the negative electrode current collector is too thick, the capacity of the entire nonaqueous electrolyte secondary battery may be too low, and conversely, if it is too thin, handling may be difficult.
[0115] In order to improve the bonding effect with the negative electrode active material layer formed on the surface, it is preferable to roughen the surface of the negative electrode current collector in advance. Examples of the surface roughening method include blasting, rolling with a rough-surface roll, mechanical polishing in which the current collector surface is polished with an abrasive cloth with abrasive particles fixed thereto, a grindstone, an emery buff, a wire brush equipped with a steel wire, or the like, electrolytic polishing, chemical polishing, and the like.
[0116] In addition, in order to reduce the mass of the negative electrode collector and improve the energy density per unit mass of the battery, a perforated type negative electrode collector such as an expanded metal or a punched metal can be used. The mass of this type of negative electrode collector can be freely changed by changing the aperture ratio. In addition, when a negative electrode active material layer is formed on both sides of this type of negative electrode collector, the rivet effect through the holes makes it even more difficult for the negative electrode active material layer to peel off. However, if the aperture ratio is too high, the contact area between the negative electrode active material layer and the negative electrode collector becomes small, and the adhesive strength may be reduced.
[0117] The slurry for forming the negative electrode active material layer is usually prepared by adding a binder, a thickener, etc. to the negative electrode material. In this specification, the term "negative electrode material" refers to a material in which the negative electrode active material and the conductive material are combined.
[0118] The content of the negative electrode active material in the negative electrode material is usually 70% by mass or more, particularly 75% by mass or more, and usually 97% by mass or less, particularly 95% by mass or less. If the content of the negative electrode active material is too small, the capacity of the secondary battery using the obtained negative electrode tends to be insufficient, and if it is too large, the content of the conductive material is relatively insufficient, making it difficult to ensure the electrical conductivity of the negative electrode. When two or more negative electrode active materials are used in combination, the total amount of the negative electrode active materials should be set to satisfy the above range.
[0119] Examples of the conductive material used in the negative electrode include metal materials such as copper and nickel; and carbon materials such as graphite and carbon black. These may be used alone or in any combination and ratio of two or more. In particular, it is preferable to use a carbon material as the conductive material, since the carbon material also acts as an active material. The content of the conductive material in the negative electrode material is usually 3% by mass or more, preferably 5% by mass or more, and usually 30% by mass or less, preferably 25% by mass or less. If the content of the conductive material is too small, the conductivity tends to be insufficient, and if it is too large, the content of the negative electrode active material, etc. is relatively insufficient, which tends to reduce the battery capacity and strength. When two or more conductive materials are used in combination, the total amount of the conductive materials should be set to satisfy the above range.
[0120] Any binder can be used for the negative electrode as long as it is safe against the solvent and electrolyte used in the manufacture of the electrode. Examples include polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, styrene-butadiene rubber-isoprene rubber, butadiene rubber, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, etc. These may be used alone or in any combination and ratio of two or more. The content of the binder is usually 0.5 parts by mass or more, preferably 1 part by mass or more, and usually 10 parts by mass or less, preferably 8 parts by mass or less, per 100 parts by mass of the negative electrode material. If the content of the binder is too small, the strength of the resulting negative electrode tends to be insufficient, and if it is too large, the content of the negative electrode active material, etc. will be relatively insufficient, which will result in insufficient battery capacity and conductivity. When two or more binders are used in combination, the total amount of the binders should be set to satisfy the above range.
[0121] Examples of thickeners used in the negative electrode include carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, etc. These may be used alone or in any combination and ratio of two or more. A thickener may be used as needed, but when used, it is preferable that the content of the thickener in the negative electrode active material layer is usually in the range of 0.5 mass% or more and 5 mass% or less.
[0122] The slurry for forming the negative electrode active material layer is prepared by mixing the negative electrode active material with a conductive material, a binder, and a thickener as necessary, and using an aqueous solvent or an organic solvent as a dispersion medium. As the aqueous solvent, water is usually used, but it is also possible to use an organic solvent such as alcohols such as ethanol and cyclic amides such as N-methylpyrrolidone in a range of 30 mass% or less with respect to water. In addition, examples of the organic solvent include cyclic amides such as N-methylpyrrolidone, linear amides such as N,N-dimethylformamide and N,N-dimethylacetamide, aromatic hydrocarbons such as anisole, toluene, and xylene, and alcohols such as butanol and cyclohexanol. Among them, cyclic amides such as N-methylpyrrolidone, linear amides such as N,N-dimethylformamide and N,N-dimethylacetamide are preferred. Note that any one of these may be used alone, or two or more may be used in any combination and ratio.
[0123] The obtained slurry is applied onto the above-mentioned negative electrode current collector, dried, and then pressed to form a negative electrode active material layer, thereby obtaining a negative electrode. The application method is not particularly limited, and a method known per se can be used. The drying method is also not particularly limited, and a known method such as natural drying, heat drying, and reduced pressure drying can be used.
[0124] <Electrode density> There are no particular restrictions on the structure of the electrode when the negative active material is made into an electrode, but the density of the negative active material present on the current collector must be less than 1 g cm -3 More than 1.2 g cm is preferable.-3 More preferably, 1.3 g cm -3 More than 2.2 g cm is particularly preferable. -3 Less than 2.1 g cm is preferable. -3 Less than 2.0 g cm is preferable. -3 Less than 1.9 g cm is more preferable. -3 The following is particularly preferred. If the density of the negative electrode active material present on the current collector exceeds the above range, the negative electrode active material particles are destroyed, which may lead to an increase in the initial irreversible capacity of the non-aqueous electrolyte secondary battery and a deterioration in high current density charge / discharge characteristics due to a decrease in the permeability of the non-aqueous electrolyte near the current collector / negative electrode active material interface. If the density is below the above range, the conductivity between the negative electrode active materials decreases, the battery resistance increases, and the capacity per unit volume may decrease.
[0125] <Conductive material> Any known conductive material can be used as the conductive material. Specific examples include metal materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; and carbonaceous materials such as amorphous carbon such as needle coke. These materials may be used alone or in any combination and ratio of two or more.
[0126] The content of the conductive material in the positive electrode active material layer is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, and is preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 15% by mass or less. When the content is within the above range, sufficient conductivity can be ensured. Furthermore, the decrease in battery capacity is easily prevented.
[0127] <Binding agent> The binder used in the production of the positive electrode active material layer is not particularly limited as long as it is a material that is stable to the nonaqueous electrolyte solution and the solvent used in the production of the electrode. In the case of the coating method, there is no particular limitation as long as the material is dissolved or dispersed in the liquid medium used in the production of the electrode. Specific examples include resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, aromatic polyamide, cellulose, and nitrocellulose; rubber-like polymers such as SBR (styrene-butadiene rubber), NBR (acrylonitrile-butadiene rubber), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers or hydrogenated products thereof, and EPDM (ethylene-propylene-diene terpolymer). Examples of suitable materials include thermoplastic elastomers such as styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers, and hydrogenated products thereof; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; and polymer compositions having ionic conductivity for alkali metal ions (especially lithium ions). These substances may be used alone or in any combination and ratio of two or more.
[0128] The content of the binder in the positive electrode active material layer is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, and also preferably 80% by mass or less, more preferably 60% by mass or less, even more preferably 40% by mass or less, and particularly preferably 10% by mass or less. When the proportion of the binder is within the above range, the positive electrode active material can be sufficiently held, and the mechanical strength of the positive electrode can be secured, so that the battery performance such as cycle characteristics is improved. Furthermore, it also leads to avoiding a decrease in battery capacity and conductivity.
[0129] <Liquid medium> The liquid medium used in preparing the slurry for forming the positive electrode active material layer is not particularly limited in type, and either an aqueous solvent or an organic solvent may be used, so long as it is a solvent capable of dissolving or dispersing the positive electrode active material, the conductive material, the binder, and the thickener used as needed. Examples of aqueous media include water, and mixtures of alcohol and water. Examples of organic media include aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; and aprotic polar solvents such as hexamethylphosphatamide and dimethylsulfoxide. These may be used alone or in any combination and ratio of two or more.
[0130] <Thickener> When an aqueous medium is used as the liquid medium for forming the slurry, it is preferable to form the slurry using a thickener and a latex such as styrene butadiene rubber (SBR). The thickener is usually used to adjust the viscosity of the slurry. There are no limitations on the thickener as long as it does not significantly limit the effects of the present invention, and specific examples include carboxymethylcellulose, methylcellulose, hydroxymethylcellulose, ethylcellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and salts thereof, etc. These may be used alone or in any combination and ratio of two or more.
[0131] When a thickener is used, the ratio of the thickener to the positive electrode active material is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 0.6% by mass or more, and preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 2% by mass or less. Within the above range, the coating property is good, and furthermore, the ratio of the active material in the positive electrode active material layer is sufficient, so that the problem of the battery capacity decreasing and the problem of the resistance between the positive electrode active materials increasing can be easily avoided.
[0132] <Consolidation> The positive electrode active material layer obtained by applying the above slurry to the current collector and drying it is preferably compacted by a hand press, roller press, or the like in order to increase the packing density of the positive electrode active material. The density of the positive electrode active material layer is 1 g cm -3 More than 1.5g cm is preferable. -3 More than 2g cm is more preferable. -3 More than 4g cm is particularly preferable. -3 Less than 3.5 g cm is preferable. -3 Less than 3g cm is more preferable. -3 The following are particularly preferred: When the density of the positive electrode active material layer is within the above range, the permeability of the non-aqueous electrolyte solution to the vicinity of the current collector / active material interface is not reduced, and the charge / discharge characteristics are good, particularly at high current densities. Furthermore, the conductivity between the active materials is less likely to decrease, and the battery resistance is less likely to increase.
[0133] <Current collector> The material of the positive electrode current collector is not particularly limited, and any known material can be used. Specific examples include metal materials such as aluminum, stainless steel, nickel plating, titanium, and tantalum; and carbonaceous materials such as carbon cloth and carbon paper. Among them, metal materials, especially aluminum, are preferred.
[0134] The shape of the current collector may be, for example, a metal foil, a metal cylinder, a metal coil, a metal plate, a metal thin film, an expanded metal, a punched metal, or a foamed metal, for example, when it is a metal material, or a carbonaceous material, a carbon plate, a carbon thin film, or a carbon cylinder, for example. Among these, a metal thin film is preferred. The thin film may be appropriately formed into a mesh shape. The thickness of the current collector is arbitrary, but is preferably 1 μm or more, more preferably 3 μm or more, even more preferably 5 μm or more, and is preferably 1 mm or less, more preferably 100 μm or less, even more preferably 50 μm or less. When the thickness of the current collector is within the above range, the strength required as a current collector can be sufficiently ensured. Furthermore, the handling property is also good.
[0135] The thickness ratio between the current collector and the positive electrode active material layer is not particularly limited, but (thickness of the active material layer on one side immediately before the injection of the nonaqueous electrolyte solution) / (thickness of the current collector) is preferably 150 or less, more preferably 20 or less, and particularly preferably 10 or less, and is also preferably 0.1 or more, more preferably 0.4 or more, and particularly preferably 1 or more. When the thickness ratio of the current collector to the positive electrode active material layer is within the above range, the current collector is less likely to generate heat due to Joule heat during high current density charge / discharge, and the volume ratio of the current collector to the positive electrode active material is less likely to increase, preventing a decrease in battery capacity.
[0136] <Electrode area> From the viewpoint of increasing the stability at high output and high temperature, the area of the positive electrode active material layer is preferably made larger than the outer surface area of the battery outer case. Specifically, the sum of the electrode areas of the positive electrodes relative to the surface area of the outer case of the nonaqueous electrolyte secondary battery is preferably 20 times or more in area ratio, and more preferably 40 times or more. In the case of a bottomed rectangular shape, the outer surface area of the outer case refers to the total area calculated from the length, width, and thickness dimensions of the case part filled with the power generating element excluding the protruding part of the terminal. In the case of a bottomed cylindrical shape, it is the geometric surface area of the case part filled with the power generating element excluding the protruding part of the terminal as a cylinder. The sum of the electrode areas of the positive electrodes refers to the geometric surface area of the positive electrode composite layer facing the composite layer containing the negative electrode active material, and in a structure in which a positive electrode composite layer is formed on both sides via a collector foil, it refers to the sum of the areas calculated separately for each side.
[0137] <Discharge capacity> When the non-aqueous electrolyte is used, the electric capacity of the battery element housed in one battery exterior of the non-aqueous electrolyte secondary battery (electric capacity when the battery is discharged from a fully charged state to a discharged state) is preferably 1 ampere hour (Ah) or more, since this increases the effect of improving low-temperature discharge characteristics. Therefore, the positive electrode plate is designed so that the discharge capacity at full charge is preferably 3 Ah (ampere hour) or more, more preferably 4 Ah or more, and also preferably 100 Ah or less, more preferably 70 Ah or less, and particularly preferably 50 Ah or less.
[0138] Within the above range, the voltage drop due to electrode reaction resistance during drawing of a large current is not too large, and deterioration of power efficiency can be prevented. Furthermore, the temperature distribution due to heat generation inside the battery during pulse charging and discharging is not too large, and the durability of the battery during repeated charging and discharging is deteriorated, and the heat dissipation efficiency is also deteriorated against sudden heat generation during abnormality such as overcharging or internal short circuit.
[0139] <Positive electrode plate thickness> The thickness of the positive electrode plate is not particularly limited, but from the viewpoint of high capacity, high output, and high rate characteristics, the thickness of the positive electrode active material layer minus the thickness of the current collector is preferably 10 μm or more, more preferably 20 μm or more, and is preferably 200 μm or less, more preferably 100 μm or less, on one side of the current collector.
[0140] <2-5. Separator> A separator is usually interposed between the positive electrode and the negative electrode to prevent short circuiting. In this case, the nonaqueous electrolyte solution of the present embodiment is usually impregnated into the separator before use.
[0141] There is no particular restriction on the material or shape of the separator, and any known material can be used as long as it does not significantly impair the effects of the present invention. Among them, it is preferable to use a material formed of a material stable to the non-aqueous electrolyte of this embodiment, such as a resin, glass fiber, or inorganic material, and to use a porous sheet or nonwoven fabric having excellent liquid retention.
[0142] Examples of materials that can be used for the resin and glass fiber separator include polyolefins such as polyethylene and polypropylene, polytetrafluoroethylene, polyethersulfone, and glass filters. Among these, glass filters and polyolefins are preferred, and polyolefins are more preferred. These materials may be used alone or in any combination and ratio of two or more.
[0143] The thickness of the separator is arbitrary, but is usually 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and is usually 50 μm or less, preferably 40 μm or less, more preferably 30 μm or less. If the separator is thinner than the above range, the insulating property and mechanical strength may be reduced. If the separator is thicker than the above range, not only may the battery performance such as rate characteristics be reduced, but also the energy density of the nonaqueous electrolyte secondary battery as a whole may be reduced.
[0144] Furthermore, when a porous material such as a porous sheet or nonwoven fabric is used as the separator, the porosity of the separator is optional, but is usually 20% or more, preferably 35% or more, more preferably 45% or more, and is usually 90% or less, preferably 85% or less, more preferably 75% or less. If the porosity is too small, the membrane resistance tends to increase and the rate characteristics tend to deteriorate. If the porosity is too large, the mechanical strength of the separator tends to decrease and the insulating properties tend to decrease.
[0145] The average pore size of the separator is also optional, but is usually 0.5 μm or less, preferably 0.2 μm or less, and usually 0.05 μm or more. If the average pore size exceeds the above range, short circuits are likely to occur. If the average pore size is below the above range, the membrane resistance increases and the rate characteristics may deteriorate.
[0146] On the other hand, examples of inorganic materials that can be used include oxides such as alumina and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates such as barium sulfate and calcium sulfate, and these are in particulate or fibrous form.
[0147] As for the form, a thin film such as a nonwoven fabric, a woven fabric, or a microporous film is used. In the thin film form, a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm is preferably used. In addition to the independent thin film form, a separator can be used in which a composite porous layer containing the inorganic particles is formed on the surface layer of the positive electrode and / or negative electrode using a resin binder. For example, a porous layer can be formed on both sides of the positive electrode using alumina particles with a 90% particle size of less than 1 μm and a fluororesin as a binder.
[0148] <2-6.Battery design> [Electrode group] The electrode group may be either a laminated structure of the positive electrode plate and the negative electrode plate with the separator interposed therebetween, or a structure in which the positive electrode plate and the negative electrode plate are spirally wound with the separator interposed therebetween. The ratio of the volume of the electrode group to the internal volume of the battery (hereinafter referred to as the electrode group occupancy rate) is usually 40% or more, preferably 50% or more, and usually 90% or less, preferably 80% or less. The lower limit of the electrode group occupancy rate is preferably set to the above range from the viewpoint of the battery capacity. Also, the upper limit of the electrode group occupancy rate is preferably set to the above range in order to secure a gap space from the viewpoint of various characteristics such as the charge / discharge repeatability and high-temperature storage as a battery, and from the viewpoint of avoiding the operation of a gas release valve that releases internal pressure to the outside. If the gap space is too small, the battery will become hot, causing the components to expand or the vapor pressure of the electrolyte liquid components to increase, resulting in an increase in internal pressure. This will degrade the battery's characteristics such as repeated charge / discharge performance and high-temperature storage performance, and may even cause the gas release valve, which releases internal pressure to the outside, to operate.
[0149] [Current collection structure] Although the current collecting structure is not particularly limited, in order to more effectively realize the improvement of the discharge characteristics by the non-aqueous electrolyte, it is preferable to adopt a structure that reduces the resistance of the wiring parts and the joint parts. When the internal resistance is reduced in this way, the effect of using the non-aqueous electrolyte is particularly well exhibited.
[0150] In the case where the electrode group has the aforementioned laminated structure, a structure formed by bundling the metal core parts of each electrode layer and welding them to a terminal is preferably used. When the area of one electrode becomes large, the internal resistance increases, so it is also preferably used to reduce the resistance by providing multiple terminals in the electrode. In the case where the electrode group has the aforementioned wound structure, the internal resistance can be reduced by providing multiple lead structures on each of the positive electrode and the negative electrode and bundling them to a terminal.
[0151] [Protection element] Examples of protective elements include PTCs (Positive Temperature Coefficients), whose resistance increases when abnormal heat is generated or excessive current flows, thermal fuses, thermistors, valves (current cutoff valves) that cut off the current flowing in the circuit due to a sudden increase in the battery's internal pressure or temperature when abnormal heat is generated, etc. It is preferable to select protective elements that will not operate under normal use at high currents, and from the perspective of high output, it is more preferable to design the battery so that abnormal heat generation or thermal runaway does not occur even without protective elements.
[0152] [Exterior body] The nonaqueous electrolyte secondary battery of this embodiment is usually configured by housing the above-mentioned nonaqueous electrolyte, negative electrode, positive electrode, separator, etc. in an exterior body (exterior case). There are no limitations on this exterior body, and any known exterior body can be used as long as it does not significantly impair the effects of the present invention.
[0153] The material of the exterior case is not particularly limited as long as it is a substance that is stable against the non-aqueous electrolyte used. Specifically, metals such as nickel-plated steel sheet, stainless steel, aluminum or aluminum alloy, magnesium alloy, nickel, titanium, etc., or a laminate film of resin and aluminum foil are preferably used.
[0154] The exterior case using the above metals includes a sealed and sealed structure formed by welding the metals together by laser welding, resistance welding, or ultrasonic welding, or a crimped structure formed by using the above metals via a resin gasket. The exterior case using the above laminate film includes a sealed and sealed structure formed by heat fusing the resin layers together. In order to improve the sealing property, a resin different from the resin used in the laminate film may be interposed between the resin layers. In particular, when the resin layer is heat-sealed via the current collecting terminal to form a sealed structure, the joining between the metal and the resin is performed, so that a resin having a polar group or a modified resin into which a polar group has been introduced is preferably used as the interposed resin.
[0155] The shape of the exterior body may also be arbitrary, and may be, for example, cylindrical, rectangular, laminated, coin-shaped, large, or the like.
[0156] <2-7. Battery break-in> [First charge] The non-aqueous electrolyte secondary battery thus prepared is subjected to an initial charge. As charging conditions, for example, the upper limit voltage is preferably 3.5 to 4.4 V. At a voltage lower than 3.5 V, the effect of improving the discharge capacity tends to be insufficient, and at a voltage higher than 4.4 V, lithium may be precipitated on the negative electrode, resulting in a decrease in capacity. The charging current is preferably in the range of 2 C or less. At a current higher than 2 C (1 C refers to a current value that requires one hour for charging or discharging. The same applies below), the effect of improving the discharge current tends to be insufficient. Furthermore, if the time from the completion of the assembly of the non-aqueous electrolyte secondary battery to the start of the initial charge is long, the productivity decreases, so it is preferable to perform the initial charge within 5 days.
[0157] In the embodiment of the present invention, the initial charge is performed in a temperature environment equal to or higher than room temperature, specifically, in a temperature environment in the range of 25°C to 60°C. By performing the initial charge in a temperature environment in the range of 25°C to 60°C, the discharge capacity can be further improved. At temperatures lower than 25°C, the effect of improving the discharge capacity tends not to be sufficiently obtained, and at temperatures higher than 60°C, the negative electrode film may dissolve and the initial characteristics may deteriorate. Therefore, by performing the initial charge in a temperature environment in the range of 25°C to 60°C, the nonaqueous electrolyte secondary battery has excellent initial characteristics.
[0158] [Storage in a high temperature environment (aging process)] The non-aqueous electrolyte secondary battery that has been initially charged as described above is stored in a high-temperature environment (hereinafter, this may be referred to as "aging (step)"). For example, the battery voltage is preferably 3.5V or higher, more preferably 3.55V or higher, and particularly preferably 3.6V or higher as a storage condition in a high-temperature environment. On the other hand, the upper limit is preferably 4.4V or lower, more preferably 4.3V or lower, and particularly preferably 4.2V or lower. At a voltage lower than 3.5V, the reduction reaction does not occur on the negative electrode surface, so the effect of improving the initial characteristics may not be sufficiently obtained. In addition, there is a relationship between the battery voltage and the state of charge (SOC), and the SOC can be used instead of the battery voltage as a storage condition in a high-temperature environment. The SOC can be obtained using a charge / discharge curve of the non-aqueous electrolyte secondary battery based on the battery voltage. For example, the SOC is preferably 17% or higher, more preferably 22% or higher, and particularly preferably 30% or higher. On the other hand, the upper limit is preferably 98% or lower, more preferably 96% or lower, and particularly preferably 95% or lower. If it is lower than 17%, the reduction reaction does not occur on the negative electrode surface, so the effect of improving the initial characteristics may not be sufficiently obtained. If it is higher than 98%, an excessive film is formed on the negative electrode surface, so the resistance increases and the battery output may decrease. The storage time in a high-temperature environment is preferably 12 hours or more, more preferably 14 hours or more, and particularly preferably 16 hours or more. On the other hand, the upper limit is preferably 200 hours or less, more preferably 150 hours or less, and particularly preferably 100 hours or less. If it is shorter than 12 hours, the reduction reaction does not occur sufficiently on the negative electrode surface, so the effect of improving the initial characteristics may not be sufficiently obtained. If it is longer than 200 hours, an excessive film is formed on the negative electrode surface, so the resistance increases and the battery output tends to decrease. As for the storage temperature in a high-temperature environment, the lower limit is preferably 50°C or more, more preferably 55°C or more, and particularly preferably 60°C or more. On the other hand, the upper limit is preferably 80°C or less, more preferably 75°C or less, and particularly preferably 70°C or less. At temperatures below 50°C, the reduction reaction of the electrolyte on the negative electrode surface becomes non-uniform, resulting in variation in the amount of film formed on the negative electrode surface, and resulting in the coexistence of areas on the negative electrode surface with both areas with a large amount of film and areas with a small amount of film.If the above-mentioned input / output test is carried out under such conditions, the resistance at the portion with a large amount of film is high, and the battery output may decrease. At temperatures higher than 80°C, the negative electrode film formed during the first charge tends to dissolve, resulting in a decrease in initial characteristics. Therefore, by storing the battery in a temperature environment within the above range, the reduction reaction of the electrolyte on the negative electrode surface occurs uniformly, and a uniform film is formed on the negative electrode surface, resulting in a nonaqueous electrolyte secondary battery with excellent initial characteristics.
[0159] The change in the battery voltage when stored in a high-temperature environment, particularly when stored for 24 hours in a high-temperature environment of 50°C or higher, preferably 60°C to 80°C, is preferably 33mV or higher, more preferably 35mV or higher, and particularly preferably 40mV or higher. On the other hand, the upper limit is preferably 100mV or lower, more preferably 75mV or lower, and particularly preferably 50mV or lower. If it is less than 33mV, the reduction reaction does not occur sufficiently on the negative electrode surface, so that the effect of improving the initial characteristics may not be sufficiently obtained. If it is more than 100mV, an excessive film is formed on the negative electrode surface, so that the resistance increases and the battery output may decrease.
[0160] In order to reinforce the film on the surface of the negative electrode, the nonaqueous electrolyte secondary battery after the battery break-in operation may be stored in a high-temperature environment several times. EXAMPLES
[0161] The present invention will be explained in more detail below by way of examples and reference examples, but the present invention is not limited to these examples as long as it does not depart from the gist of the present invention.
[0162] <Examples 1-1 to 1-4 and Comparative Examples 1-1 to 1-8> [Preparation of negative electrode] 98 parts by mass of natural graphite was mixed with 1 part by mass of an aqueous dispersion of sodium carboxymethylcellulose (concentration of sodium carboxymethylcellulose: 1% by mass) and 1 part by mass of an aqueous dispersion of styrene-butadiene rubber (concentration of styrene-butadiene rubber: 50% by mass) as a thickener and binder, and the mixture was mixed in a disperser to form a slurry. The obtained slurry was applied to one side of a copper foil having a thickness of 10 μm, dried, and pressed to form a negative electrode.
[0163] [Preparation of positive electrode] Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 85 parts by mass of 102O2, 10 parts by mass of acetylene black as a conductive material, and 5 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone solvent with a disperser to form a slurry. This was evenly applied to one side of an aluminum foil with a thickness of 15 μm, dried, and pressed to form a positive electrode.
[0164] [Preparation of non-aqueous electrolyte] In a dry argon atmosphere, dried LiPF6 was dissolved in a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) (volume ratio 30:35:35) to give a ratio of 1.1 mol / L to prepare basic electrolyte 1. FSO3Li, LiPO2F2, and LiBOB were added to basic electrolyte 1 prepared above to prepare the nonaqueous electrolytes shown in Table 1 below. The concentration of fluorosulfonate ions [FSO3 - ] and the concentration of difluorophosphate ion [PO2F2 - ] and the concentration of bis(oxalate)borate ions [BOB - ] is indicated.
[0165] [Manufacture of non-aqueous electrolyte secondary batteries] The above positive electrode, negative electrode, and polyethylene separator were laminated in the order of negative electrode, separator, and positive electrode to prepare a battery element. This battery element was inserted into a bag made of a laminate film of aluminum (thickness 40 μm) coated on both sides with a resin layer while the positive and negative terminals were protruding, and the above prepared nonaqueous electrolyte was then injected into the bag and vacuum sealed to prepare a laminate type nonaqueous electrolyte secondary battery.
[0166] [Battery break-in] The non-aqueous electrolyte secondary battery was sandwiched between glass plates to enhance adhesion between the electrodes, and in a thermostatic chamber at 25°C, the non-aqueous electrolyte secondary battery was charged at a constant current-constant voltage (hereinafter referred to as CC-CV charging) to 4.2V at a current equivalent to 1 / 6C, and then discharged to 2.5V at 1 / 6C. CC-CV charging was performed to 4.1V at 1 / 6C. Then, aging was performed under conditions of 60°C, 24 hours or 45°C, 24 hours. Then, the non-aqueous electrolyte secondary battery was discharged to 2.5V at 1 / 6C to stabilize it. Furthermore, CC-CV charging was performed to 4.2V at 1 / 6C, and then discharged to 2.5V at 1 / 6C to perform battery break-in operation. In this example, in order to investigate the effect of the storage temperature in the aging process on the initial output characteristics after the end of the battery break-in operation, the initial output characteristics of the batteries that were run-in at two different storage temperatures were compared and evaluated. In addition, it was confirmed by the results of ion chromatography that the composition of the non-aqueous electrolyte at the time of preparation satisfies formula (1) even after the aging process.
[0167] [Evaluation of initial output characteristics] The batteries after the evaluation of the battery break-in were charged to 3.72V at 25°C with a constant current of 1 / 6C. They were discharged at 0.5C, 1.0C, 1.5C, 2.0C, and 2.5C at -20°C, and the voltage was measured after 5 seconds. The resistance value (Ω) was calculated from the slope of the current-voltage line. Table 1 shows the relative value (%) when the resistance value (reference resistance value) of Example 1-1 when aging was performed under the conditions of 60°C and 24 hours was set to 100.0. In this example, from the viewpoint of practicality, the resistance value when aging was performed under the conditions of 60°C and 24 hours was equal to or less than the reference resistance value was considered to be acceptable.
[0168] [Table 1]
[0169] As is clear from Table 1, [FSO3 - ]>[PO2F2 - ]>[BOB - ] has excellent initial output characteristics. Furthermore, when the storage temperature is 45°C, the change in battery voltage before and after storage is less than 33 mV, whereas when the storage temperature is 60°C, the change in battery voltage before and after storage is 33 mV or more. - ]>[PO2F2 - ]>[BOB - When the relationship of [FSO3 - ]>[PO2F2 - ]>[BOB - ] is satisfied, and compared with the case where the storage temperature is 60° C. (the case where the storage temperature is 60° C. in Examples 1-1 to 1-4), the initial output characteristics are deteriorated. Also, [FSO3 - ]>[PO2F2 - ]>[BOB - ] is not satisfied (Comparative Examples 1-1 to 1-8), [FSO3 - ]>[PO2F2 - ]>[BOB - It can be seen that the relationship of FSO3 is satisfied, and the initial output characteristics are reduced regardless of the storage temperature, as compared to when the storage temperature is 60°C (when the storage temperature is 60°C in Examples 1-1 to 1-4). - , PO2F2 - and B.O.B. - It was shown that by using a nonaqueous electrolyte solution with a content within a specific range and by ensuring that the voltage change during storage in a high-temperature environment is 33 mV or more, the output characteristics of a nonaqueous electrolyte secondary battery in a low-temperature environment can be improved.
[0170] <Examples 2-1 to 2-4 and Comparative Examples 2-1 to 2-7> [Preparation of negative electrode] A negative electrode was produced in the same manner as in Example 1-1, except that the slurry containing the negative electrode active material was applied to both sides of the copper foil.
[0171] [Preparation of positive electrode] Li(Ni 0.5 Mn 0.3 Co 0.2 90 parts by mass of 100% ethylene oxide, 7 parts by mass of acetylene black as a conductive material, and 3 parts by mass of polyvinylidene fluoride (PVdF) as a binder were mixed in N-methylpyrrolidone solvent using a disperser to form a slurry. This was evenly applied to one side of an aluminum foil with a thickness of 15 μm, dried, and pressed to form a positive electrode.
[0172] [Preparation of non-aqueous electrolyte] The non-aqueous electrolyte solutions shown in Table 2 below were prepared in the same manner as in Example 1-1. The concentration of fluorosulfonate ions [FSO3 - ] and the concentration of difluorophosphate ion [PO2F2 - ] and the concentration of bis(oxalate)borate ions [BOB - ] is indicated.
[0173] [Manufacture of non-aqueous electrolyte secondary batteries] A non-aqueous electrolyte secondary battery was produced in the same manner as in Example 1-1.
[0174] [Battery break-in] The battery was run-in in the same manner as in Example 1-1, etc. It was confirmed from the results of ion chromatography that the composition of the non-aqueous electrolyte at the time of preparation also satisfied formula (1) after the aging process.
[0175] [Evaluation of initial output characteristics] The batteries after the evaluation of the battery break-in were charged to 3.72V at 25°C with a constant current of 1 / 6C. They were discharged at 0.5C, 1.0C, 1.5C, 2.0C, and 2.5C at -20°C, and the voltage was measured after 5 seconds. The resistance value (Ω) was calculated from the slope of the current-voltage line. Table 2 shows the relative value (%) when the resistance value (reference resistance value) when aging was performed under the condition of 60°C and 24 hours in Example 2-1 was set to 100.0. In this example, from the viewpoint of practicality, the resistance value when aging was performed under the condition of 60°C and 24 hours was equal to or less than the reference resistance value was considered to be acceptable.
[0176] [Table 2]
[0177] As is clear from Table 2, [FSO3 - ]>[PO2F2 - ]>[BOB - ] has excellent initial output characteristics. Furthermore, when the storage temperature is 45°C, the change in battery voltage before and after storage is less than 33 mV, whereas when the storage temperature is 60°C, the change in battery voltage before and after storage is 33 mV or more. - ]>[PO2F2 - ]>[BOB - When the relationship of [FSO3 - ]>[PO2F2 - ]>[BOB - ] is satisfied, and compared with the case where the storage temperature is 60° C. (the case where the storage temperature is 60° C. in Examples 2-1 to 2-4), it can be seen that the initial output characteristics are decreased. Also, [FSO3 - ]>[PO2F2 - ]>[BOB - ] is not satisfied (Comparative Examples 2-1 to 2-7), [FSO3 - ]>[PO2F2 - ]>[BOB -It can be seen that the relationship of FSO3 is satisfied, and the initial output characteristics are reduced regardless of the storage temperature, as compared to when the storage temperature is 60°C (when the storage temperature is 60°C in Examples 2-1 to 2-4). - , PO2F2 - and B.O.B. - It was shown that by using a nonaqueous electrolyte solution with a content within a specific range and by ensuring that the voltage change during storage in a high-temperature environment is 33 mV or more, the output characteristics of a nonaqueous electrolyte secondary battery in a low-temperature environment can be improved.
[0178] <Examples 3-1 to 3-4 and Comparative Examples 3-1 to 3-4> [Preparation of negative electrode] A negative electrode was produced in the same manner as in Example 1-1.
[0179] [Preparation of positive electrode] A positive electrode was produced in the same manner as in Example 1-1.
[0180] [Preparation of non-aqueous electrolyte] Under a dry argon atmosphere, aluminum fluorosulfonate (Al(FSO3)3) was diluted with ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) so that the Al ion concentration in the mixed solvent was as shown in Table 3, and the solvent composition was a volume ratio of 30:35:35 of EC, EMC, and DMC. LiPF6 was then thoroughly dried and dissolved at 1.1 mol / L (as the concentration in the non-aqueous electrolyte) to prepare basic electrolyte 2. FSO3Li, LiPO2F2, and LiBOB were added to basic electrolyte 2 prepared above to prepare the non-aqueous electrolytes shown in Table 3 below. The fluorosulfonate ion concentration [FSO3 - ] and the concentration of difluorophosphate ion [PO2F2 - ] and the concentration of bis(oxalate)borate ions [BOB - ] is indicated. In Table 3, 0 ppm Al (results containing no Al) is the result of adding FSO3 - , PO2F2 -, B.O.B. - The non-aqueous electrolyte solution shown in Table 3 was prepared by adding FSO3 - , PO2F2 - , B.O.B. - The content of indicates the amount added, and the content of Al element (Al ion) is a value obtained based on the measurement results of inductively coupled plasma atomic emission spectrometry (ICP-AES) described later. Note that the "content (mass%)" and "content (mass ppm)" in the table are the contents when the basic electrolyte 1 is taken as 100 mass%.
[0181] <Measurement of Al element content in non-aqueous electrolyte> 100 μL (approximately 130 mg) of the non-aqueous electrolyte was taken out. The taken non-aqueous electrolyte was weighed into a PTFE beaker, and an appropriate amount of concentrated nitric acid was added and wet decomposed on a hot plate, after which the volume was adjusted to 50 mL. The content of Li and Al elements was measured using an inductively coupled plasma atomic emission spectrometry (ICP-AES, Thermo Fischer Scientific, iCAP 7600duo) by the acid concentration matching calibration curve method.
[0182] [Manufacture of non-aqueous electrolyte secondary batteries] The above positive electrode, negative electrode, and polyethylene separator were laminated in the order of negative electrode, separator, and positive electrode to prepare a battery element. This battery element was inserted into a bag made of a laminate film of aluminum (thickness 40 μm) coated on both sides with a resin layer while the positive and negative terminals were protruding, and the above prepared nonaqueous electrolyte was then injected into the bag and vacuum sealed to prepare a laminate type nonaqueous electrolyte secondary battery.
[0183] [Battery break-in] The battery was run-in in the same manner as in Example 1-1, etc. It was confirmed from the results of ion chromatography that the composition of the non-aqueous electrolyte at the time of preparation also satisfied formula (1) after the aging process.
[0184] [Evaluation of initial output characteristics] The batteries after the evaluation of the battery break-in were charged to 3.72V at a constant current of 1 / 6C at 25°C. They were discharged at 0.5C, 1.0C, 1.5C, 2.0C, and 2.5C at -20°C, and the voltage was measured after 5 seconds. The resistance value (Ω) was calculated from the slope of the current-voltage line. Table 3 shows the relative value (%) when the resistance value (reference resistance value) of Example 3-1 containing 19 mass ppm of Al element is set to 100.0. In this example, from the viewpoint of practicality, the resistance value below the reference resistance value when aging was performed under the condition of 60°C for 24 hours was considered to be acceptable.
[0185] [Table 3]
[0186] As is clear from Table 3, [FSO3 - ]>[PO2F2 - ]>[BOB - When the relationship of [FSO3 - ]>[PO2F2 - ]>[BOB - ] is satisfied, and compared with the case where the Al element is contained at 19 ppm (19 ppm by mass of the element in Examples 3-1 to 3-4), it can be seen that the initial output characteristics are deteriorated. Also, [FSO3 - ]>[PO2F2 - ]>[BOB - ] is not satisfied (Comparative Examples 3-1 to 3-4), [FSO3 - ]>[PO2F2 - ]>[BOB - It can be seen that the relationship of [FSO3] is satisfied and the initial output characteristics are reduced, regardless of the inclusion of the Al element, as compared with the case where the Al element is contained at 19 ppm (19 ppm by mass in Examples 3-1 to 3-4). - , PO2F2 - and B.O.B. -It has been shown that the use of a nonaqueous electrolyte solution having a content within a specific range and containing a predetermined amount of Al ions in the electrolyte solution further improves the output characteristics of a nonaqueous electrolyte secondary battery in a low-temperature environment. [Industrial Applicability]
[0187] According to the non-aqueous electrolyte according to the embodiment of the present invention, it is possible to realize the manufacture of a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery capable of improving low-temperature output characteristics, which is useful. Therefore, the non-aqueous electrolyte according to the embodiment of the present invention and the energy device such as a non-aqueous electrolyte secondary battery using the same can be used for various known applications. Specific examples include, for example, a notebook computer, a pen-input personal computer, a mobile personal computer, an electronic book player, a mobile phone, a mobile fax machine, a mobile copy machine, a mobile printer, a headphone stereo, a video movie, a liquid crystal television, a handy cleaner, a portable CD, a mini disc, a transceiver, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, a motorized bicycle, a bicycle, a lighting device, a toy, a game device, a clock, an electric tool, a strobe, a camera, a home backup power source, a business backup power source, a load leveling power source, a natural energy storage power source, a lithium ion capacitor, and the like.
Claims
1. A non-aqueous electrolyte secondary battery comprising a non-aqueous electrolyte containing fluorosulfonate ions, difluorophosphate ions, and bis(oxalato)borate ions, The non-aqueous electrolyte solution has a fluorosulfonate ion concentration [FSO 3 - ] and the concentration of difluorophosphate ions [PO 2 F 2 - ] and the concentration of bis(oxalato)borate ions [BOB - and n is a nonaqueous electrolyte that satisfies the following formula (1): [FSO] 3 - ]>[PO 2 F 2 - ]>[BOB - ] (1)
2. 2. The nonaqueous electrolyte secondary battery according to claim 1, wherein the nonaqueous electrolyte satisfies the following formulas (2) and (3): ([FSO] 3 - ]+[PO 2 F 2 - ]) / ([PO 2 F 2 - ]+[BOB - ])>1.8 (2) [FSO 3 - ]<1.3 mass % (3)
3. 3. The nonaqueous electrolyte secondary battery according to claim 1, wherein the voltage change when the nonaqueous electrolyte secondary battery is stored at a voltage of 4.1 V in a high temperature environment of 60° C. or higher for 24 hours is 33 mV or more.
4. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein the nonaqueous electrolyte contains Al ions in an amount of 1 ppm by mass to 100 ppm by mass.
5. A non-aqueous electrolyte secondary battery comprising a negative electrode and a positive electrode capable of absorbing and releasing lithium ions, and the non-aqueous electrolyte according to any one of claims 1 to 4.
6. 6. The nonaqueous electrolyte secondary battery according to claim 5, wherein the positive electrode has a positive electrode active material layer on a current collector, and the positive electrode active material layer contains at least one selected from the group consisting of a lithium-cobalt composite oxide, a lithium-cobalt-nickel composite oxide, a lithium-manganese composite oxide, a lithium-cobalt-manganese composite oxide, a lithium-nickel composite oxide, a lithium-nickel composite oxide, a lithium-nickel-manganese composite oxide, and a lithium-cobalt-nickel-manganese composite oxide.
7. A method for producing a non-aqueous electrolyte secondary battery comprising a non-aqueous electrolyte solution containing fluorosulfonate ions, difluorophosphate ions, and bis(oxalato)borate ions, The concentration of fluorosulfonate ions in the nonaqueous electrolyte solution [FSO 3 - ] and the concentration of difluorophosphate ions [PO 2 F 2 - ] and the concentration of bis(oxalato)borate ions [BOB - a battery assembly process for assembling a nonaqueous electrolyte secondary battery using a nonaqueous electrolyte solution in which an aging step of aging the nonaqueous electrolyte secondary battery in a temperature environment in the range of 50° C. or higher and 80° C. or lower. [FSO] 3 - ]>[PO 2 F 2 - ]>[BOB - ] (1)
Citation Information
Patent Citations
Nonaqueous electrolyte and nonaqueous electrolyte secondary battery
JP2016184462A
Nonaqueous electrolyte secondary battery
JP2019050153A
Electrolyte, electrochemical device, lithium ion secondary battery, and module
JP2019102434A
Nonaqueous electrolyte secondary battery
JP2019212419A
Electrolyte for non-aqueous electrolyte cell, and non-aqueous electrolyte cell in which same is used
WO2017111143A1